Heterologous expression of DobHLH25 from Dendrobium officinale enhances drought tolerance in Arabidopsis - Qingxia Liu; Jian Wang; Yan Zhang; Rong Wang; Youya Liu; Jingzhong Chen; Bo Wang; Ningmei Chen; Qingwen Sun; Ronghui Gu; Yuan Huang (Functional & Integrative Genomics, 2026)

Conjugation-enhanced porous aromatic framework enables pore-confined photocatalytic conversion of uranyl into studtite for uranium extraction - Huazhen Rong; Handan Wen; Jiashun Mao; Yue Ma; Xiaohui Yan; Min Luo; Tao Liu; Yihui Yuan; Ning Wang (Desalination, 2026)

Chronic toxicity of triazine-based and non-triazine ultraviolet filters toward Chlorella vulgaris: Low ecological risk of triazine-based compounds - Yuhao Yan; Hong Gao; Rundong Chen; Zhigang Wang; Cheng Zeng; Jia Yuan; Jianjun Liu; Rong Chen (Bioresource Technology, 2026)

Impacts of high-altitude aerosol hygroscopicity on cloud microphysics in the North China Plain: A WRF fast-SBM modeling study - Qian Gao; Hui He; Xiang'e Liu; Yan Yang; Rong Yuan; Ping Tian; Kai Bi; Fei Wang; Jiujiang Sheng; Yongqing Wang (Atmospheric Research, 2026)

Immunotherapy in multiple myeloma: advances from immune microenvironment insights to clinical application - Yao Zhang; Yuting Lei; Yanzhao Huang; Yan Gao; Rong Liu; Kaiyun Guo; Chunlian Zhao; Ming Lei (Molecular Biology Reports, 2026)

MiR-4327 targets TP53 to promote cervical cancer cell proliferation - Mei-Lin Chen; Chen-Yang Chu; Feng-Xian Zhang; Li-Pei Zhang; Ying Yang; Bai-Zhao Peng; Chuang-Hai Wu; Xiao-Mei Chen; Yan-Ting You; Bing-Ying Rong; Hiu Yee Kwan; Xiao-Shan Zhao; et al. (Functional & Integrative Genomics, 2026)
Cervical cancer is a leading cause of female malignancy worldwide. While microRNA-4327 (miR-4327) has been implicated as a potential oncogene, its functional role and molecular mechanisms in cervical cancer pathogenesis remain unclear. This study aimed to determine the oncogenic function of miR-4327 and elucidate its downstream regulatory mechanism in cervical cancer pathogenesis. We measured miR-4327 expression in clinical cervical cancer tissues and cell lines using quantitative real-time PCR (qRT-PCR). We then assessed its effects on proliferation, migration, invasion, and cell cycle progression through functional assays including cell counting kit-8 (CCK-8), colony formation, transwell, and flow cytometry. To evaluate tumor growth in vivo, we established a xenograft model in non-obese diabetic (NOD)-severe combined immune-deficient (scid) mice. Using bioinformatic analysis and luciferase reporter assays, we identified TP53 as a direct target of miR-4327 and further validated this regulatory relationship with gain- and loss-of-function experiments. We found that miR-4327 was significantly upregulated in cervical cancer and promoted malignant phenotypes such as proliferation, migration, invasion, and cell cycle progression in vitro. Consistent with this, overexpression of miR-4327 accelerated tumor growth in vivo. Mechanistically, we confirmed TP53 as a direct functional target of miR-4327. Knocking down TP53 phenocopied the oncogenic effects of miR-4327, while restoring TP53 expression rescued the tumor-promoting effects mediated by miR-4327. These findings reveal a novel miR-4327/TP53 regulatory axis and nominate miR-4327 as a potential therapeutic target for intervention.

Root accumulation and efficient translocation of steroids in mangrove plants: Implications for an overlooked coastal reservoir - Ji-Xun Chen; Nian-Nian Wu; Shan Liu; Yuan Liu; Qin-Ge Zhou; Qing-Song Yang; Juan Ling; Xiao-Fang Huang; Yan-Kuan Tian; Chang-Gui Pan; Xiang-Rong Xu (Marine Pollution Bulletin, 2026)

Pathogenic mechanisms of Trichoderma hamatum, a postharvest pathogen causing fruit rot - Hai-Rui Wang; Xiong Xiong; Wen-Chao Li; Shuang-Jiao Ma; Yan-Xue Liu; Tong Liu; Ke-Xiang Gao; Chuan-Rong Li; Hui-Xiang Liu; Ye-Han Tian (Postharvest Biology and Technology, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Co-optimization of cross-domain enhancement and frequency-domain decoupling: An engineering-oriented framework for underwater dam crack detection - Chuan Lin; Rongfeng Liu; Weiwei Lin; Rong Xiao; Yan Su (Engineering Structures, 2026)

Selective removal of fluoxetine by a core-shell molecularly imprinted TiO2 photocatalyst: degradation mechanism and toxicity mitigation - Ding Pan; Xin-Yi Jiao; Peng Liu; Jing-Hao Yang; Jing-Jun Qin; Cai-Shan Wang; Ying-Zhi Ding; Xue-Rong Wang; Yan-Chao Jin; Xin-Hui Liu; Zhang Liu; Li-Ping Li (Chemical Engineering Journal, 2026)

Regional assessment of multi-pool mangrove carbon across five coastal provinces of China: Heterogeneity, carbon accounting, and contextual screening - Yan Zheng; Wenhai Lu; Chang Liu; Hefeng Wang; Rong Zeng; Yan Xu; Yangyi Ai (Regional Studies in Marine Science, 2026)

DNA methylome analysis reveals EjABCG23-mediated epigenetic regulation underlying fruit russeting in white-fleshed loquat - Kun Zhang; Yuying Ding; Rong Su; Chang Liu; Xuelian Li; Yang Wang; Yan Deng; Qiong Zhou; Xiaojun Chen; Yuxing Li; Qunxian Deng (Postharvest Biology and Technology, 2026)

Robust retrieval of inland water nitrogen and phosphorus: De-biasing satellite-in situ matchups and integrating environmental constraints - Xihua Wang; Xingyu Zhu; Y. Jun Xu; Yongjiu Feng; Rong Huang; Chenyi Shi; Chengming Luo; Boyang Mao; Shunqing Jia; Qinya Lv; Zejun Liu; Xuming Ji; et al. (Journal of Water Process Engineering, 2026)

Intensive anthropogenic activities control the spatiotemporal heterogeneity of river eutrophication at the watershed scale - Xihua Wang; Shunqing Jia; Y. Jun Xu; Chaomeng Dai; Nianqing Zhou; Zejun Liu; Boyang Mao; Qinya Lv; Xuming Ji; Chengming Luo; Yan Dai; Yanxin Rong (Journal of Hydrology, 2026)

Cu-based MOFs@TiO2/PVDF composite membrane for efficient oil-water separation and bacterial isolation and sterilization - Lin-Lin Liu; Xue-Ling Zeng; Xuan Shi; Yu-Zhuo Fan; Wen-Yan Zeng; Ze-Hui Bai; Rong-Ke You; Xue-Qin Zhan; Fang-Chang Tsai; Ning Ma (Journal of Environmental Chemical Engineering, 2026)

Associations of serum lithium, nickel, cobalt, and manganese with chronic kidney disease among Chinese older adults: Mediating role of lipid metabolism and moderating effect of lifestyle - Yan Wang; Qingping Liu; Wenyuan Zhu; Xiaoqing Ma; Tao Zhang; Mengqi Zou; Mengruo Wang; Lei Bao; Yaxian Pang; Tao Jing; Rong Zhang (Environmental Pollution, 2026)

Endoplasmic reticulum stress-mediated glycophagy drives macrophage M1 polarization in silica nanoparticles-induced pulmonary fibrosis - Lei Bao; Zihan Geng; Linpeng Niu; Lili Shi; Liyi He; Yaxian Pang; Cunhui Zhang; Yan Liu; Jiawei Chen; Beibei Shi; Ruiting Wu; Jingyuan Wang; et al. (Journal of Environmental Sciences, 2026)

PhySimNet: Accelerating PDE simulations with physics-integrated learning - Qi Wang; Yuan Mi; Mengtao Yan; Yang Liu; Ji-Rong Wen; Hao Sun (Computer Physics Communications, 2026)

Botany, extraction methods, chemical constituents, pharmacological activities, and food applications of Stauntonia chinensis - Chen-Yu Chang; Xiao-Yun Wang; Ke-Jia Liu; Qi Li; Shu-Yan Lu; Qin-Ge Ma; Rong-Rui Wei (Natural Product Research, 2026)

Evaluating the effectiveness of marine ecological red lines: an integrated assessment of ecological outcomes and governance performance - Rong Zeng; Wenhai Lu; Chengliang He; Jie Liu; Yan Xu; Chang Liu; Yangyi Ai; Yan Zheng (Frontiers in Marine Science, 2026)
Marine protected areas worldwide often exhibit uneven conservation outcomes, largely due to differences in governance effectiveness and management implementation. As a large-scale spatial conservation policy, Marine Ecological Red Lines (MERLs) have been widely implemented in China to regulate human activities and safeguard critical marine ecosystems. However, their protection effectiveness remains insufficiently evaluated using quantitative and scalable approaches. In this study, we develop an indicator-based assessment framework grounded in the Pressure–State–Response (PSR) model to evaluate the effectiveness of MERLs. The framework integrates indicators of anthropogenic pressures, ecosystem conditions, and management responses, enabling spatially explicit and temporally comparable assessment. We apply this framework to MERLs in Hainan Province over a five-year period (2020–2024) and conduct systematic comparisons with adjacent non-protected areas. Furthermore, correlation analysis is used to examine the relationships between pressure reduction and ecological state changes, providing preliminary insight into the associations between management actions and ecological outcomes. The results show that MERLs are associated with reduced anthropogenic pressures and improved ecological conditions relative to surrounding areas, although spatial heterogeneity in outcomes persists. The proposed framework provides a structured approach for examining interactions among pressures, ecosystem states, and governance responses, and provides quantitative evidence supporting conservation effectiveness assessment at a provincial scale. The proposed framework may also support adaptive management and policy optimization for MERLs and provide practical reference for the implementation of Other Effective Area-Based Conservation Measures (OECMs).

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Burkholderia cepacia NB-13: Biocontrol efficacy and medium-driven metabolic regulation - Zhou Yin; Xiaoqin Li; He Guan; Dindi Tu; Xingyi Luo; Wancheng Hu; Fanqian Zhou; Menglong Li; Shulin Liu; Hui Li; Rong Song; Kailin Liu; et al. (Pesticide Biochemistry and Physiology, 2026)

Climate change during the early Middle Jurassic: Evidence from coal-bearing strata of the Ordos Basin - Nian-De Shang; Jing-Jing Liu; Shi-Feng Dai; Ian T. Graham; Qiu-Chan Han; Rong-Kun Jia; Jia-Wei Feng; Meng-Da Yao; Yan Wang (Palaeoworld, 2026)

Polystyrene nanoplastics induce neuroinflammation-driven depression-like behaviors in mice via the HIF-1α–NAT10–ac4C-mediated glycolytic activation - Yan Liu; Linpeng Niu; Cunhui Zhang; Lei Bao; Mengruo Wang; Qingping Liu; Hao Liu; Zhaohui Hu; Lili Shi; Yaxian Pang; Rong Zhang; Yujie Niu (Journal of Environmental Sciences, 2026)

Impacts of urban open space environments on residents' health: A perspective on potentially toxic metals in dust - Yue Zeng; Qiang Ban; Junjie Yu; Changchun Qiu; Yajie Jiang; Xinyu Liu; Dian Lin; Shiqi Yan; Yunqin Li; Binxin Wu; Wei Yu; Rong Yu (Environmental Pollution, 2026)

Optimizing lipid retention for anaerobic membrane bioreactors treating food waste: Balancing methane enhancement and membrane fouling control - Luwei Yan; Shuangquan Zhao; Yu Xi; Yaqian Liu; Yuxin Xiao; Zhen Lei; Qian Li; Rong Chen (Bioresource Technology, 2026)

Wenyang Yishen Tongluo prescription synergizes with bone marrow mesenchymal stem cells to alleviate rheumatoid arthritis via inhibiting IL-6 - Rong Su; Shiyun Yin; Lingli Gu; Weichao Liu; Weitian Yan; Weijian Zhou; Jiangyun Peng (Journal of Molecular Histology, 2026)

An Indicator System for Evaluating the Powerhouse of Meteorological Science and Technology: Design and Preliminary Application - Chaolin Zhang; Xudong Liang; Min Wen; Jianjun He; Wenjuan Zhang; Chang Liu; Qing Sun; Rong Yu; Xiaolu Yan; Zhu Zhang; Qihua Jin; Aili Shi; et al. (Journal of Meteorological Research, 2026)

Study on the anti-inflammatory effects of active ingredients in Vespa velutina auraria Smith - Ming-Rong Li; Xiu-Qin Pang; Chao-He Liu; Wei Zhang; Heng Liu; Hai-Rong Zhao; Zhi-Bin Yang; Yan Wang; Yi-Hao Che; Huai Xiao (Natural Product Research, 2026)

Quantifying the light interception and canopy photosynthesis of strip intercropping system based on 3D canopy photosynthesis model - Si-Rong Huang; Qing-Feng Song; Zheng Guo; Qiu-Feng Long; Li-Sha Zhang; Yue Li; Yuan Yang; Xiao-Chun Wang; Feng Yang; Tai-Wen Yong; Jiang Liu; Yan-Hong Yan; et al. (Computers and Electronics in Agriculture, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Integrated metabolomic and transcriptomic analyses reveal that pectin metabolism mediates texture divergence in grape berries - Zhi-Meng Gan; Xiao-Yan Ai; Yong Liu; Wei Zhu; Yang Zhang; Hui-Liang Wang; Fu-Rong Wang; Xiao-Dong Hou; Hua-Ping He; Lin-Zhong Gong (Postharvest Biology and Technology, 2026)

A novel closed-loop path planning algorithm for unmanned surface vessel swarms based on potential field-guided deep Q-learning - Chunhan Zhang; Rong Zhen; Yu Zheng; Yan Zhang; Jialun Liu; Ke Zhang; Chunxu Li (Ocean Engineering, 2026)

PM2.5 exposure exacerbates cerebral infarction via HPG axis downregulation and pituitary lipid metabolism dysregulation in mice - Xin lv; Guanhui Pei; Lijuan Liu; Zhou zhou; Yicong Zhou; Binbin Wang; Chaoyue Meng; Ruomeng Chen; Qiang Yao; Ge Bai; Xuelin Wang; Minghan Zhao; et al. (NeuroToxicology, 2026)

Dual-engineered defect-rich molecularly imprinted zirconium metal organic framework platform for selective adsorption and ultrasensitive analysis of alternariol - Shi-Rong Sun; Lu Liu; Xia Wang; Yan Dong; Yan Li; Qianyun Sun; Yanfang Zhao; Xiangfeng Chen; Yong-Ning Wu; Rabah Boukherroub; Ru-Song Zhao (Journal of Hazardous Materials, 2026)

A novel mitochondrial OMA1-DELE1-HRI axis mediates polystyrene microplastics-induced blood-testis barrier dysfunction - Rong Wang; Zhen Tian; Chen Chen; Ming-Ming Zhang; Ding-Qiang Peng; Ke-Xin Liu; Yu-Tong Ren; Shuai Lin; Qiang Hong; Yan-Li Ji; Yuan-Hua Chen (Journal of Environmental Sciences, 2026)

Distribution of plutonium in a ternary system of water-colloid-bentonite: Implications for radionuclide migration - Yan Liu; Chun Zhang; Yu Wang; Hui Xu; Rong Gong; Jianzheng Zang; Jianbo Liu; Xiang Zhou (Journal of Contaminant Hydrology, 2026)

Depth-dependent attachment and transport of bacteriophages MS2 and ΦX174 in saturated soils: Impacts of silt and clay fraction - Xue-yan Hao; Ying Han; Ying Song; Rong-xuan Xu; Shuang Xu; Ming-da Liu (Journal of Contaminant Hydrology, 2026)

Molecular characterization of a novel partitivirus isolated from Fusarium solani, the causal agent of tobacco root rot - Xiao Wu; Ying Wang; Rui Guo; Ya Rong Wang; Si Jun Li; Xiang Ping Zhou; Jie Zhong; Yan Song Xiao; Tian Bo Liu (Archives of Virology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Exosome-mediated delivery of non-classical effectors in Geotrichum citri-aurantii manipulates citrus immunity via PTI-ETI cascade and ROS burst - Yan Wu; Rong Liu; Fen Zhang; Di Wang; Qingjun Kong; Xueyan Ren (Postharvest Biology and Technology, 2026)

Ganoderma lucidum spore lipid extract synergizes with chemotherapy to alleviate tumor progression by enhancing macrophage phagocytosis of dying tumor cells - Guan-Di Xiao; Zi-Xuan Li; Yi-Fang Li; Lei Liang; Cheng Yuan; Wen-Dong Xu; Ju-Yan Liu; Yan-Ping Wu; Rong-Rong He (PharmaNutrition, 2026)

Association of phthalate exposure during early pregnancy with fetal growth and the effect modification by gestational stress - Nian Wu; Zhongmei Hu; Xinyi Xiao; Shimin Xiong; Xingyan Liu; Yan Xie; Rong Zeng; Kunming Tian; Xubo Shen; Yuanzhong Zhou; Yijun Liu (International Journal of Hygiene and Environmental Health, 2026)

Engineering catalytic sites in ZnIn2S4 via Mg doping: A S-to-In shift toward enhanced photocatalytic H2 evolution - Yan Wang; Yuqi Shi; Xin Chong; Chao Wang; Rong Fu; Chang Liu; Yuelan Zhang (Chemical Engineering Journal, 2026)

Enhanced tellurium recovery via ultrasonic-assisted alkaline leaching-electrodeposition with integrated alkali regeneration - Su Yan; Shixing Wang; Libo Zhang; Rong Zhu; Xinrui Yang; Hongliang Liu; Jianqiang Ye; Guowei Luo; Yonggang Zuo; Gengwei Zhang; Guo Lin; Likang Fu (Chemical Engineering Journal, 2026)

A germline-specific vesicular structure licenses mRNA activation during spermiogenesis and is hijacked in gastric cancer - Mingxi Liu; Zerui Wang; Yinuo Li; Qingsong Xie; Zhuang Xiao; Xuezhi He; Guanxiong Wang; Yang Gao; Yini Zhang; Lin Zheng; Xun Xia; Lujie Chen; et al. (Science Bulletin, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

When city lights turn blue: Spectral ALAN exposure, LED lighting, and diabetes prevalence using SDGSAT-1 - Yanqing Xu; Ruoyu Dong; Tingting Li; Sujin Zhang; Yan Liu; Yuchen Li; Kenan Li; Xiaobo Feng; Shuang Rong (Environmental Pollution, 2026)

Corrigendum to “Flooding duration affects the temperature sensitivity of soil extracellular enzyme activities in a lakeshore wetland in Poyang Lake, China” [Sci. Total. Environ., Volume 874 (2023), 162397] - Xingyun Huang; Kexin Wang; Xiuting Wen; Jie Liu; Yan Zhang; Jun Rong; Ming Nie; Chun Fu; Bofu Zheng; Zhifen Yuan; Ruichang Shen (Science of The Total Environment, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Subversion of redox homeostasis in citrus by the Geotrichum citri-aurantii effector GcSP2 via targeting GDP-mannose pyrophosphorylase 1 - Rong Liu; Yan Wu; Di Wang; Haijue Zhang; QingJun Kong; Xueyan Ren (Postharvest Biology and Technology, 2026)

Two new menthane monoterpene derivatives isolated from Hypericum monogynum - Yan-Rong Zeng; Hong-Jin Ban; Jing-Yi Yin; Zhan Feng; Ya-Nan Li; Yan Liu; Xiao-Jiang Hao; Chun-Mao Yuan (Phytochemistry Letters, 2026)

Tarsus-enriched chemosensory proteins in Achelura yunnanensis (Lepidoptera, Zygaenidae) and their interactions with pesticides - Fu-Peng Li; Zi-Hui Liu; Xiao-Rong Xiong; Jin-Lan Zhang; Hai-Yan Xiao; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2026)

Bidirectional electron transfer enabled by dual electric fields for efficient 4-nitrophenol removal on a bifunctional FeCoNiP/PCN heterojunction - Yan Wang; Chang Liu; Rong Fu; Chao Wang; Xin Chong; Yuqi Shi; Yuelan Zhang (Journal of Environmental Chemical Engineering, 2026)

Development of a high-throughput sensitive SB-PCR assay for rapid detection of laboratory-escaped antibiotic resistance genes - Lingfeng Yan; Shengnan Liu; Rong Cao; Azadeh Nilghaz; Jiajin Wei; Hehui Long; Liming Zhang; Zhuoxuan Lu (Journal of Environmental Chemical Engineering, 2026)

Hybrid prediction framework for total nitrogen in freshwater lake watershed based on the northern goshawk optimization and multiple machine learning methods: An integrated strategy from data cleaning to model optimization - Xihua Wang; Chengming Luo; Y. Jun Xu; Shunqing Jia; Zejun Liu; Boyang Mao; Yan Dai; Yanxin Rong; Qinya Lv; Xuming Ji (Journal of Environmental Chemical Engineering, 2026)

Coupled in-situ H2O2 generation and utilization over donor-acceptor covalent organic frameworks for rapid photocatalytic U(VI) removal - Huazhen Rong; Jiashun Mao; Yue Ma; Xiaohui Yan; Min Luo; Handan Wen; Tao Liu; Yihui Yuan; Ning Wang (Desalination, 2026)

Bioinspired interfacial anchoring enables durable ultra-black photothermal coatings based on silica-coated carbon nanotubes - Jian Li; Yan Wang; Xiaolong Wu; Chao Li; De-Rong Sun; Peng Wang; Zimu Li; Xue-Qing Liu (Chemical Engineering Journal, 2026)

The Study of Modified Lignite Residue As Methylene Blue Adsorbent In Water: Preparation and Mechanism - Yan Yu; Qidong Wu; Yu Qin; Rong Liu; Tiancai Zheng (Water, Air, & Soil Pollution, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

New mechanistic insights into the antiviral candidate CA-P: Activation of plant redox-mediated defense and suppression of virus biosynthesis - Rong-Shuang Luo; Yan-Wei Huang; Yu-Cheng Gu; Long Cheng; Wu-Bin Shao; Yan-Mei Liao; Qian Guo; Dan Zeng; Hong-Mei Xiang; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; et al. (Pesticide Biochemistry and Physiology, 2026)

Mechanism of synergistic astringency enhancement by organic acids in model wine: Insights from organic acid-phenols-protein triadic interaction - Yan Liu; Xiang Jie Jiang; Shi qing Zhang; Qing hao Zhao; Yue fan Zhao; Wan Rong Zhao; Shi Yi Peng; Guo Rong Du; Xiao Yuan; Peng Tao Zhao; Xiao Yu Wang (Food Chemistry, 2026)

Occurrence, composition profiles, and human exposure assessment of liquid crystal monomers in indoor dust from Wuxi, China - Yiyang Yao; Linlin Wu; Run Zhou; Xi Wang; Yan Gong; Rong Chen; Wenwei Liu (Environmental Pollution, 2026)

High-performance fiber-based aerogel evaporator for solar desalination and wastewater purification - Yan Liang; Siqi Wu; Yujie Zhao; Ning Liu; Rong Tian; Jianbin Zhang; Yanhua Liu; Dianming Li; Libang Feng (Desalination, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

Intensive anthropogenic activities drive dynamic surface water-groundwater interactions: Implications for contaminant pathways at a catchment scale - Shunqing Jia; Xihua Wang; Y. Jun Xu; Chaomeng Dai; Nianqing Zhou; Zejun Liu; Boyang Mao; Qinya Lv; Xuming Ji; Chengming Luo; Yan Dai; Yanxin Rong (Journal of Contaminant Hydrology, 2026)

Deciphering runoff-sediment-nutrient dynamics in agricultural watersheds supplied by large feeder Rivers: A multi-scale analysis - Xihua Wang; Xuming Ji; Y. Jun Xu; Boyang Mao; Shunqing Jia; Zejun Liu; Qinya Lv; Chengming Luo; Yan Dai; Yanxin Rong (Journal of Contaminant Hydrology, 2026)

Cataract Aggravates Alzheimer-Like Pathologies and Cognitive Deficits in an APP/PS1 Mouse Model - Zhao Geng; Zhong-Yuan Yu; Jun Tan; Xuan-Yue Wang; Gui-Hua Zeng; Jiang-Hui Li; Yu-Di Bai; Xiao-Qin Zeng; Yu-Peng Zhu; Cheng-Rong Tan; An-Yu Shi; Yu-Hui Liu; et al. (Neuroscience Bulletin, 2026)
Clinical investigations have suggested a potential link between cataracts and Alzheimer’s disease (AD). However, whether cataract has an impact on the progression of AD remains unclear. The objective of this research was to determine the relationship between cataracts and AD. A cataract model was established in APP/PS1 [mutant amyloid precursor protein (APP) and a mutant presenilin-1 (PS1) gene] mice via lens puncture. Behavioural assays were used to evaluate cognitive function. Immunohistochemistry, immunofluorescence, and enzyme-linked immunosorbent assays (ELISA) were applied to detect AD-related pathology. Visual signals were markedly obstructed following surgery to induce cataracts, and these mice presented an increased cerebral amyloid-beta (Aβ) load, while no significant alterations in the levels of enzymes associated with Aβ metabolism were detected. In addition, compared with control mice, cataract model mice presented increased astrogliosis and microgliosis, along with elevated levels of proinflammatory factors. Moreover, cataract model mice presented more pronounced cognitive impairments than did control mice. Our study offers experimental confirmation that cataract considerably contributes to the pathogenesis of AD, thereby emphasizing the importance of visual signals in maintaining cognitive well-being.

Metagenomic and metatranscriptomic characterization of syntrophic propionate- and butyrate-oxidizing bacterial communities in Qiangyong proglacial lake sediments on the Qinghai-Tibet Plateau - Rong Wen; Hongfei Chi; Meiling Feng; Yang Zhao; Chengfang Ma; Keshao Liu; Qi Yan; Pengfei Liu (Soil Ecology Letters, 2026)

Microwave-enhanced carbothermal reduction for efficient recovery of valuable metals from spent lithium-ion batteries - Gui-Rong Zhang; Da-Shuai Li; Xing-Yu Huang; Yuan-Long Liu; Yan-Qing Cheng; Ling Tong (Waste Management, 2026)

Plantation type regulates molecular characteristics and chlorine reactivity of soil-derived DOM: Enhanced DBPs formation in legume plantations - Xin-Yi Jiao; Su-Ping Liu; Cai-Shan Wang; Ying-Zhi Ding; Shuang Peng; Zi-Hao Wu; Yan-Chao Jin; Peng Liu; Ding Pan; Xue-Rong Wang; Dong-Bin Wei; Xin-Hui Liu; et al. (Journal of Hazardous Materials, 2026)

Divergence in anthropogenic activities contributed to the eutrophication heterogeneity between river and lake at basin scale: new insights from trophic state index in Asia's largest basin (Yangtze River) - Yan Dai; Xihua Wang; Y. Jun Xu; Qinya Lv; Xuming Ji; Boyang Mao; Shunqing Jia; Zejun Liu; Chengming Luo; Yanxin Rong (Journal of Contaminant Hydrology, 2026)

Corrigendum to “a sandwich-structured anisotropic conductive film with robust interfacial reliability and conductivity for functional electrical interconnections” [chemical engineering journal 505 (2025): 159721/CEJ_159721] - Yang Liu; Yan Pan; Zeyu Zheng; Hebin Zhang; Rong Sun; Pengli Zhu (Chemical Engineering Journal, 2026)

Taxonomy and phylogeny of Erysiphe species on Liquidambar formosana (Hamamelidaceae) - Jing Feng; Shuang-Bao Wang; Shu-Yan Liu; Michael Bradshaw; Uwe Braun; Shou-Rong Yu; Guan-Xiu Guan; Dan-Ni Jin; Zhao-Yang Zhang; Han-Xing Gao (New Zealand Journal of Botany, 2025)

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Rainfall, seasonal variation, and stream type governing the multi-media fate and ecological risks of tire additives and their transformation products in mega-urban streams - Li-Ni Wei; Nian-Nian Wu; Ru Xu; Yuan Liu; Shan Liu; Hai-Yan Zhang; Zi-Tong Li; Yue-Hong Liu; Xiang-Rong Xu; Jian-Liang Zhao; Guang-Guo Ying (Water Research, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Labdane-type diterpenoids from Hypoestes phyllostachya inhibit pancreatic cancer stem cells - Tong Yan; Lin-Fen Ding; Ya Chen; Guo-Xian Hu; Lu Qu; Ming Hu; Ya-Xuan Ma; Rong-Qing Yuan; Lin Jia; Mei-Ju Zhao; Liu-Dong Song; Jia Su; et al. (Phytochemistry, 2025)

Metallurgical organic pollutants assisted source apportionment of mobile heavy metals on artisanal non-ferrous metal processing contamination - Li-Rong Liu; Junyao Yan; Lei Xiang; Ting Liu; Ye Xiao; Wen-Shen Liu; Wen-Jun Wu; Ping Li; Miaoyue Zhang; Yuan-Qing Chao; Ye-Tao Tang; Rong-Liang Qiu (Journal of Hazardous Materials, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

Correction: Regulatory effect of AMP-activated protein kinase on pulmonary hypertension induced by chronic hypoxia in rats: in vivo and in vitro studies - Xiaoying Huang; Rong Fan; Yuanyuan Lu; Chang Yu; Xiaomei Xu; Xie Zhang; Panpan Liu; Shuangquan Yan; Chun Chen; Liangxing Wang (Molecular Biology Reports, 2025)

Cholesterol and 24S-OHC Induce Neuronal Apoptosis and Necroptosis, but Not Ferroptosis Despite Elevated Iron Levels - Yinghui Li; Tingbin Xu; Jiahua Yang; Rong Liu; Yan Qu; Jun Wang (Molecular Neurobiology, 2025)

Comprehensive study of W06A7.4 and TMEM144 mediated pathways in aging: insights from Caenorhabditis elegans to human - Li Fang Wang; Xiaorong Liu; Sisi Li; Rong Li; Ran Li; Fengxia Yan; Xi Jing (Molecular Genetics and Genomics, 2025)

The high-affinity K+ transporter IbHAK5 enhances potassium ion absorption and improves root morphology in sweetpotato (Ipomoea batatas) - Rong Jin; Peng Zhao; Mengxiao Yan; Ming Liu; Weijuan Fan; Qiangqiang Zhang; Xiaoya Zhu; Jing Wang; Yongchao Yu; Jun Yang; Hongxia Wang; Zhonghou Tang (Transgenic Research, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Investigation of the Shallow Structure of the Hami Basin Northern Margin Fault Using Comprehensive Geophysical Methods - Guang-hong Ju; Xiao-dong He; Rong-ying Zheng; Yan-ling Liu; Jun-qi Duan; Jun Shen; Zhi-tao Gao (Applied Geophysics, 2025)

ESG Scores and financial performance are making energy companies be in a dilemma: evidence from China - Fang-rong Ren; Hui-yi Chen; Xi-ting Yang; Xin-ge Guan; Xiao-yan Liu (Environment, Development and Sustainability, 2025)

Prediction of ammonia and total nitrogen in large freshwater lake watershed based on small sample data and analysis of their spatiotemporal variation and driving mechanism - Chengming Luo; Xihua Wang; Y. Jun Xu; Shunqing Jia; Zejun Liu; Boyang Mao; Qinya Lv; Xuming Ji; Yanxin Rong; Yan Dai (Process Safety and Environmental Protection, 2025)

A BrDof2.4-BrHDA6 module is involved in ABA-CTK-mediating leaf yellowing in Chinese flowering cabbage by affecting histone H3 and H4 acetylation of CCGs - Zhen-liang Mou; Lei Yan; Zong-li Liu; Xin-guo Su; Ze-xiang Zeng; Yuan Rong; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Wei Wei; Jia Si (Postharvest Biology and Technology, 2025)

Iridoids and other constituents from the aerial parts of Patrinia rupestris and their inhibitory effects on nitric oxide production - Zhi-Yuan Liu; Sheng-Run Guo; Jian-Xian Tang; Chun-Yan Zhao; Li Pu; Li-Zhong Wang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Phytochemistry, 2025)

Hypocalcemia as biological mechanism responsible for prenatal exposure to polycyclic aromatic hydrocarbons (PAHs) and anemia: Insights from Zunyi birth cohort - Lei Luo; Wenbi Yang; Haonan Zhang; Lei Bai; Zhongbao Chen; Lin Tao; Haiyan Wang; Shimin Xiong; Ruoxuan Li; Yijun Liu; Xingyan Liu; Yan Xie; et al. (Journal of Environmental Sciences, 2025)

Unraveling nitrogen evolution characteristics and driving mechanisms of estuarine alluvial islands - Xihua Wang; Yanxin Rong; Y. Jun Xu; Qinya lv; Xuming Ji; Boyang Mao; Shunqing Jia; Zejun Liu; Chengming Luo; Yan Dai (Journal of Contaminant Hydrology, 2025)

The dynamic succession of the core microbial communities in pasteurized milk during refrigeration based on metagenomics - Chunyan Hu; Rong Guo; Jiao Zhuang; Yan Gao; Xia Zhang; Yu Meng; Zhen Liu; Yongxia Bian; Liqing Wu; Shuai Guo; Ning Ju (International Dairy Journal, 2025)

Janus-structured thermally conductive radiative cooler for electronic devices heat dissipation - Xiuyan Yan; Jinru Liu; Linping Zhang; Yi Zhong; Bolin Ji; Wei Wu; Bijia Wang; Xueling Feng; Liduo Rong; Hong Xu; Zhiping Mao (Chemical Engineering Journal, 2025)

Three new triterpenoids from the fruit of Eleutherococcus senticosus (Rupr.) Harms - Yan Liu; Yu-Xuan Lin; Xiao-Hui Rong; Meng-Meng Li; Juan Pan; Wei Guan; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2025)

Navigating the lunar frontier: one hundred landing sites at the south pole for future mission challenges - Yongjiu Feng; Pengshuo Li; Haoteng Li; Yan Liu; Mengrong Xi; Rong Wang; Shurui Chen; Panli Tang; Yuze Cao; Qian Huang; Qionghua You; Shijie Liu; et al. (Science Bulletin, 2025)

Unveiling the mystery of eutrophication prediction for large freshwater lake through Temporal Convolutional Network hybrid model - Chengming Luo; Xihua Wang; Y. Jun Xu; Shunqing Jia; Zejun Liu; Boyang Mao; Yan Dai; Yanxin Rong; Qinya Lv; Xuming Ji (Journal of Environmental Chemical Engineering, 2025)

Study on the reaction mechanism of nitrogen-containing gases from polyurethane pyrolysis with carbonate molten salts - Yang-Hai Zheng; Jun-Qiang Rui; Sheng-Rong Guo; Cheng Yao; Zhao-Yang Liu; Yun Xue; Ju-Yue Yang; Yong-De Yan (Fuel, 2025)

Neuroprotective Effects, Mechanisms of Action and Therapeutic Potential of the Kv7/KCNQ Channel Opener QO-83 in Ischemic Stroke - Huiran Zhang; Yanfei Tian; Yan Zhang; Yan Wang; Jinlong Qi; Xiangyu Wang; Yi Yuan; Rong Chen; Yupeng Zhao; Chang Liu; Najing Zhou; Lanxin Liu; et al. (Translational Stroke Research, 2025)

OsR126 IncRNA integrates AtWRKY46 and AtEM1 into ABA signaling in Arabidopsis - Lingyun Chang; Shengyi Liu; Nan Zhang; Dongxu Yang; Ziguang Liu; Hongli Yuan; Rong Yan; Xingguo Lan; Yasushi Yukawa; Juan Wu (Plant Cell Reports, 2025)

Introduce multivariate two-dimensional information to establish a data-driven volume estimation model for complex microplastic fibers - Zhan-Ao Zhang; Rong Zhang; Rui Gan; Runqi Liu; Xuxiang Zhang; Yan Zhang (Science of The Total Environment, 2025)

Impact of intensive human activities on nitrate pollution in river basins: A spatiotemporal isotopic analysis - Shunqing Jia; Xihua Wang; Y. Jun Xu; Zejun Liu; Boyang Mao; Qinya Lv; Xuming Ji; Chengming Luo; Yan Dai; Yanxin Rong (Journal of Water Process Engineering, 2025)

Phthalocyanine-based nanosensitizers for enhanced sonodynamic therapy activity of hypoxic tumor with dual apoptosis/ferroptosis pathways - Xue-Yan Li; Jin Liu; Bi-Yuan Zheng; Mei-Rong Ke; Jian-Dong Huang (Journal of Photochemistry and Photobiology B: Biology, 2025)

H3K18 lactylation drives the progression of silica nanoparticles-induced pulmonary fibrosis via promoting macrophage M1 polarization - Lili Shi; Lin Zhang; Zhenfang Ma; Zhaohui Hu; Zihan Geng; Hao Liu; Jingyuan Wang; Ke Feng; Yiheng Geng; Yan Liu; Cunhui Zhang; Yujia Xie; et al. (Journal of Hazardous Materials, 2025)

Dual-quantification of the different contributions of climate change and anthropogenic activities to eutrophication of rivers and lakes in Asia's largest river basin (Yangtze River) - Xihua Wang; Yan Dai; Y. Jun Xu; Qinya Lv; Xuming Ji; Boyang Mao; Shunqing Jia; Zejun Liu; Chengming Luo; Yanxin Rong (Journal of Hazardous Materials, 2025)

Nanoplastics under the charge effects: Unveiling the potential threats to amphibian (Rana nigromaculata) growth, intestinal damage and microbial ecology - Peng Fang; Shuzi Ye; Zidie Luo; Rong Guo; Yan Jiang; Lemei Liu; Siwen Li; Fang Xiao (Environmental Pollution, 2025)

Study on the field-scale bacterial growth dynamics and ecological effects of microbial dust suppression - Haoran Wang; Yi He; Rong Liu; Jie Chen; Yongjiang Wen; Kunyu Yan; Yong Cao (Chemical Engineering Journal, 2025)

Protein/polysaccharide composite nanocoating based on amyloid-like aggregation for fresh-cut fruits preservation - Guichen Liu; Rong Liu; Chengyu Fu; Xiang Hu; Ke Li; Luke Yan; Peng Yang; Jian Zhao (Chemical Engineering Journal, 2025)

Bio-organic fertilizer application improves cucumber growth, disease resistance, and soil fertility by regulating rhizosphere microbiomes - Junyan Yang; Xin Liu; Xiangmin Rong; Pan Jiang; Yixiang Xia; Guixian Xie; Gongwen Luo; Xiaoyuan Yan (Plant and Soil, 2025)

Effects of Land-Use Change on Soil Infiltrability and Preferential Flow in Typical Low Hilly Area - Linlin Chu; Rong Ma; Yue Liu; Yan Zhao; Lidong Bi; Chen Dan (Journal of Soil Science and Plant Nutrition, 2025)

Limited leaf thermal acclimation but higher tolerance in subtropical trees after 10-year translocation in Dinghushan biosphere reserve - Ting Wu; David T Tissue; Wei Su; Honglang Duan; Mark G. Tjoelker; Sachin G. Chavan; Shuyidan Zhou; Junfeng Yuan; Liang Fang; Mengxiao Yu; Shizhong Liu; Guowei Chu; et al. (Agricultural and Forest Meteorology, 2025)

Nitrite Toxicity in Shrimp Aquaculture: Mechanisms, Health Impacts, and Sustainable Mitigation Strategies - Dan‐Dan Bian; Yan‐Xia Shi; Xue Zhang; Xin Liu; Jun‐Jie Jiang; Xi‐Rong Zhu; Dai‐Zhen Zhang; Qiu‐Ning Liu; Bao‐Jian Zhu; Bo‐Ping Tang (Reviews in Aquaculture, 2025)
The rapid expansion of intensive aquaculture systems has caused escalating environmental challenges due to excessive nitrogenous waste accumulation, which surpasses the metabolic capacity of aquatic microbiota and elevates nitrite concentrations. As a pervasive environmental toxin, nitrite induces oxidative stress, disrupts metabolic homeostasis, and compromises gut microbiota and immune function in shrimp, leading to mass mortality, economic losses, and ecological disruption. These impacts threaten both aquaculture productivity and ecological sustainability. This review synthesizes three decades of research to elucidate the multifactorial mechanisms of nitrite toxicity, including genotoxicity, apoptosis, growth impairment, and dysregulated cellular signaling pathways. Key findings highlight that nitrite overload impairs mitochondrial function, dysregulates apoptosis pathways, and interferes with growth and reproductive processes, thereby undermining shrimp development and reproduction. To address these challenges, the review evaluates emerging mitigation strategies such as antioxidant‐enriched feeds, probiotic modulation, and biofloc technology, which optimize nitrogen cycling, enhance detoxification capacity, restore microbial equilibrium, and improve survival rates in experimental trials. Unlike prior fragmented studies, this review integrates mechanistic insights into nitrite toxicity with scalable interventions, proposing a novel decision framework for system‐specific nitrite management. This framework offers actionable recommendations for policymakers and industry stakeholders to balance aquaculture productivity with ecological sustainability. By advancing the understanding of nitrite's ecotoxicological impacts, this review charts a path toward resilient and sustainable aquaculture systems, transforming mechanistic insights into preventive protocols and offering a holistic perspective on nitrite pollution control that reconciles economic objectives with ecological sustainability.

Orchard variable rate spraying method and experimental study based on multidimensional prescription maps - Chenming Hu; Yu Ru; Shuping Fang; Zifan Rong; Hongping Zhou; Xianghai Yan; Mengnan Liu (Computers and Electronics in Agriculture, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Inactivation performance of virus and bacterium in water by dielectric barrier discharge coupled with pulse corona discharge plasma - Pengcheng Yan; Rong Zhang; Min Zhang; Chang Wen; Yuxin Cheng; Zhenghui Liu; Guangzhou Qu; Ronghua Li; Tiecheng Wang; Fei Ling (Journal of Water Process Engineering, 2025)

Bridging the knowledge gap: From poly(butylene adipate-co-terephthalatebutylene) degradation to CO2-generating mineralization under the synergistic effect of bacteria and fungi - Yue Wang; Qi Liu; Chang-Hong Xie; Ruo-Tong Zhao; Qiu-Xiang Tang; Dong-Fei Han; Yi-Ning Xia; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

Transcriptome analysis reveals the molecular mechanisms of the 8-day infection cycle of Ecytonucleospora hepatopenaei in Litopenaeus vannamei and the host's molecular responses - Yan Rong; Yi Qiao; Tingyue Liu; Xiaohui Cao; Ge Jiang; Jie Cheng; Huiwen Jiang; Xianping Fan; Hui Shen (Fungal Biology, 2025)

Facile fabrication of ethyl cellulose/gelatin fibers incorporated with copper-based metal-organic frameworks as humidity-triggered release of carvacrol for blueberry preservation - Jing Xie; Xingyu Rong; Xiaoqian Jiang; Yuping Zhao; Tianhua Ding; Jing Yan; Suqing Li; Wen Qin; Mingrui Chen; Yaowen Liu (Food Chemistry, 2025)

Direct recovery of high-purity uranium from fluoride-containing nuclear wastewater via extraction materials with ensemble Lewis sites and a tandem electrochemical device - Guo Li; Yan Liu; Chi Jiao; Zhengyu Jiang; Juan Zhang; Tao Chen; Tao Lin; Rong He; Wenkun Zhu; Xiangke Wang (Water Research, 2025)

Associations between serum trace elements and biological age acceleration in the Chinese elderly: A community-based study investigating the mediating role of inflammatory markers and the moderating effect of physical activity - Yan Wang; Wenyuan Zhu; Tao Zhang; Qingping Liu; Mengqi Zou; Yujia Xie; Mengruo Wang; Tian Shuai Wang; Yaxian Pang; Tao Jing; Rong Zhang (Journal of Hazardous Materials, 2025)

Degradation of biodegradable plastic films in soil: microplastics formation and soil microbial community dynamics - Yue Wang; Run-Hao Bai; Qi Liu; Qiu-Xiang Tang; Chang-Hong Xie; Aurore Richel; Christophe Len; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

Ultra-sensitive, versatile and portable detection of hydrazine in eco-environmental systems using a smartphone-integrated ratiometric fluorescent sensor - Xiao-Hong Li; Meng-Zhao Li; Xiao-Yan Yang; Tian-Yan Wang; Yin-Heng Luo; WMWW Kandegama; Jing-Yi Li; Ge-Fei Hao; Chun-Rong Liu (Journal of Hazardous Materials, 2025)

Characteristics of nitrogen and phosphorus migration at sediment-water interface in seasonal frozen lakes and the mechanism of microbial driven cycling: a case study of Lake Daihai - Rong Wu; Xiaohong Shi; Xueer Kang; Sheng Zhang; Shengnan Zhao; Yu Liu; Biao Sun; Junping Lu; Haifeng Yu; Shihuan Wang; Xueru Pan; Kaiqi Shen; et al. (Journal of Contaminant Hydrology, 2025)

Multi-machine learning methods for rapid and synergistic inversion of groundwater contamination source, hydrogeologic parameter and boundary condition - Chengming Luo; Xihua Wang; Y. Jun Xu; Qinya Lv; Xuming Ji; Boyang Mao; Shunqing Jia; Zejun Liu; Yanxin Rong; Yan Dai (Journal of Contaminant Hydrology, 2025)

PtBi nanocatalysts with controlled chain-like structure and composition: Solvothermal synthesis and ethanol oxidation performance - Luo-Yi Yan; Han-Tao Zhang; Xiao-Yu Lu; Li-Ming Liu; Rong-Hua Zhang; Zheng Cheng; Shuai-Wei Fan; Xin-Wen Zhou (Fuel, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Single and joint associations of exposure to polycyclic aromatic hydrocarbons with hypertensive disorders of pregnancy: A nested case-control study - Rui Yu; Cheng Chen; Mingyu Deng; Nian Wu; Yanling Xiao; Songlin An; Lin Tao; Xingting Zheng; Jing Yang; Zhongmei Hu; Pei Xu; Xingyan Liu; et al. (Environmental Pollution, 2025)

Collaborative mechanism of microbial fuel cell native bacteria and Sporosarcina pasteurii: Improving mineralization performance - Jin-Di Liu; Wei-Min Cheng; Xiang-Ming Hu; Xiao Li; Yue Feng; Yan-Yun Zhao; Ming-Yue Wu; Hui Rong; Xiao-Niu Yu; Yin-Bo Xiang; Zhi-Rong Zhang (Chemical Engineering Journal, 2025)

Type-A and -C response regulator genes positively impact rice plant height and panicle architecture - Chenyu Rong; Renren Zhang; Jing Xie; Jieru Li; Tiantian Yan; Ziyu Liu; Yuexin Liu; Ruihan Xu; Xi’an Shi; Xuebin Zhao; Jiali Song; Yayi Meng; et al. (Plant Cell Reports, 2025)

Characteristics of loess landslides under the effects of faults and rivers and their correlations with geological and surficial evolutionary processes - Qi-qi Liu; Wan-li Xie; Hui Yang; Ming Yan; Rong-sen Zhu; Ke Mu; Yi-lun Chang; Shengjie Di; Xiaoliang He; Xiaomin Liu; Ying Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Adsorption behavior and mechanism of cadmium, copper, and lead on polylactic acid microplastics exposed to ultraviolet light - Fang Feng; Shutao Wang; Xue He; Xinghua Wang; Jia Huang; Guiming Liu; Sashuang Rong; Shiming Su; Hongyuan yan; Bing Han; Wei Liu (Journal of Environmental Chemical Engineering, 2025)

Theoretical insights into electrochemical CO2 reduction by Bi-based catalysts: single crystals versus mixed phases - Mengting Zhou; Hongxia Liu; Juntao Yan; Qingjun Chen; Huiping Zhao; Rong Chen; Lei Liu (Chemical Engineering Journal, 2025)

Glymphatic Impairment Associated with Neurocognitive Dysfunction in Moyamoya Disease - Chaofan Zeng; Yuanren Zhai; Peicong Ge; Chenglong Liu; Xiaofan Yu; Wei Liu; Junsheng Li; Qiheng He; Xingju Liu; Xun Ye; Qian Zhang; Rong Wang; et al. (Translational Stroke Research, 2025)

Effect of high in-situ asymmetric stress on the brittle failure of the boundary of an underground powerhouse - Ben-Guo He; Shi-Chen Qiu; Xia-Ting Feng; En-Rong Liu; Tao Chen; Shencun Yan (Bulletin of Engineering Geology and the Environment, 2025)

Subseasonal Prediction Skill in the CAMS-CSM Subseasonal-to-Seasonal Forecast System - Yuhan Yan; Jingzhi Su; Boqi Liu; Libin Ma; Xinyao Rong; Bo Liu; Yanli Tang; Jian Li (Advances in Atmospheric Sciences, 2025)

Wind Direction and Strength Determine the Genetic Structure of an Insect‐Pollinated Plant Across Heterogeneous Landscape - Jun‐Yin Deng; Rong‐Hua Fu; Stephen G. Compton; Chuan Yuan; Matthew M. Kling; Xiao‐Yong Chen; Yao‐Bin Song; Kai Jiang; Mei Liu; Jaco M. Greeff; Yan Chen (Journal of Biogeography, 2025)
Aim Dispersal of plant propagules and their genes is crucial for plant responses to landscape heterogeneities, yet the mechanisms behind this dispersal remain unclear. Ficus species depend on wind‐borne fig wasps for pollination, but research on airflow effects on Ficus genetic structure has produced conflicting results. Our study aims to clarify the role of wind in shaping the genetic structure of such plants with wind‐borne insect pollinators by examining how geomorphological complexity interacts with air movements to influence genetic structures. Location Southwest China: Sichuan, Yunnan, Guangxi and Guizhou provinces. Taxon Ficus tikoua Bur., Ficus , Moraceae. Methods We sampled 56 F. tikoua sites across southwest China, characterised by high geomorphologic complexity. River basins and predominant winds were visualised across the sampled regions. Wind connectivity between sampled sites during the main pollination season was modelled based on hourly daily wind data. The maternal and biparental genetic structure of sites were reconstructed using chloroplast DNA (cpDNA) and nuclear SSR (nuSSR) markers. Links between genetic structure, location, and wind parameters were estimated by Mantel or partial Mantel tests. Results The plant's maternal genetic structure was defined by river systems, with two distinct cpDNA groups located in the Yangtze and Pearl River basins, respectively. The boundaries for nuclear variation were less clearly delimited geographically. Sites with mixtures of nuSSR groups were concentrated where prevailing winds arrived from several directions. Stronger between‐site air flows increased nuSSR geneflow and genetic similarities, while populations receiving more wind flow were also more genetically variable. Main Conclusions Our study reveals how plant gene dispersal reflects air and water movements that in turn respond to geomorphologic complexity, thereby directly demonstrating the effects of wind on gene flow of plants with wind‐borne insect pollinators. Wind data matching pollinator flight times and large sample sizes are crucial for testing wind effects.

Variation in climate and hydrological conditions in Southwest China during the mid-to-late Holocene, inferred from stalagmite multiple proxies - Hua-Yan Li; Yao Wu; Ting-Yong Li; Rong Duan; Hai-Bo Wang; Jia-Hui Cui; Chao-Jun Chen; Yue Jin; Yue-Hua Xiang; Zi-Qi Liu; Jun-Yun Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Foliar-applied zinc promotes cadmium allocation from leaf surfaces to grains in rice - Ya-Ting Liu; Bo-Fang Yan; Xuan Cai; Hong-Xiang Zheng; Rong-Liang Qiu; Ye-Tao Tang (Journal of Environmental Sciences, 2025)

Hydrothermal synthesis of Ag-Mn@ZSM-5: An effective catalyst for catalytic oxidation of chlorobenzene - Yan Tan; Xiao Liu; Yujia Zhang; Yiyang Rong; Xueying Wu; Ting Liu; Zizhen Ma; Huawei Zhang (Fuel, 2025)

Au-isolated Pt active site with enhanced C-H bond activation ability for selective oxidation of polyol to hydroxyl acid - Xuewei Ding; Ying Liao; Rong Fan; Hao Yan; Xin Zhou; Xiang Feng; Xiaobo Chen; Hui Zhao; Yibin Liu; Chaohe Yang (Chemical Engineering Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

SIRT5: a potential target for discovering bioactive natural products - Yuwei Xie; Nali Cai; Xiaohua Liu; Liangliang He; Yiming Ma; Changyu Yan; Juan Liang; Shu-Hua Ouyang; Ao Luo; Yingzhi He; Jun Lu; Dang Ao; et al. (Journal of Natural Medicines, 2025)
Silent information regulator 5 (SIRT5) is the fifth member of the sirtuin family, which is mainly expressed in mitochondrial matrix. SIRT5 plays a key role in metabolism and antioxidant responses, and is an important regulator for maintaining intracellular homeostasis. Given its involvement in multiple cellular processes, dysregulation of SIRT5 activity is associated with a variety of diseases. This review explores the structural characteristics of SIRT5 that influence its substrate specificity, highlights recent research advances, and summarizes its four key enzymatic activities along with their corresponding substrates in disease contexts. We also discuss the natural products that modulate SIRT5 activity and identify potential targets of SIRT5 through virtual docking, which may provide new therapeutic avenues. Although the mechanism of SIRT5 in diseases needs to be further elucidated and deglutathionylation activities are still at an early stage, targeting SIRT5 and its substrates holds significant promise for the development of novel therapeutics. Graphical abstract

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Combining POA-VMD for multi-machine learning methods to predict ammonia nitrogen in the largest freshwater lake in China (Poyang Lake) - Chengming Luo; Xihua Wang; Y. Jun Xu; Cong Wang; Qinya Lv; Xuming Ji; Boyang Mao; Shunqing Jia; Zejun Liu; Yanxin Rong; Yan Dai (Journal of Water Process Engineering, 2025)

Construction of phenothiazine-decorated ZnO quantum dots with intelligent response to bacterial pH/amidase microenvironment for inducing bacterial ferroptosis-like death - Wu-Bin Shao; Rong-Shuang Luo; Yan-Wei Huang; Long Cheng; Dan Zeng; Xiang Zhou; Li-Wei Liu; Song Yang (Chemical Engineering Journal, 2025)

Single-cell atlas profiling revealed cellular characteristics and dynamic changes after PD-1 blockade therapy of brain metastases from laryngeal squamous cell carcinoma - Yunzhi Zou; Hao Duan; Zekun Deng; Rong Xiang; Jixiang Zhao; Zhenhua Zhang; Wanming Hu; Yuanzhong Yang; Zeming Yan; Shujuan Wen; Zexian Liu; Gao Zhang; et al. (Molecular and Cellular Biochemistry, 2025)
Brain metastasis (BM) in laryngeal squamous cell carcinoma (LSCC) is uncommon but prognosis is poor. Anti-PD-1 immunotherapy benefits some advanced LSCC cases, yet its efficiency is limited by tumor complexity. We analyzed paired metastatic tumor samples from before and after immunotherapy using single-cell RNA sequencing (scRNA-seq), along with a primary LSCC dataset and bulk RNA sequencing. This identified changes post-immunotherapy and revealed differences in single-cell transcriptomes among LSCC, primBM, and neoBM. Our findings show that anti-PD-1 treatment suppresses metastasis-promoting pathways like VEGF and EMT in cancer cells, and alters immune cell functions. Notably, it upregulates T cell activation, leading to CD8 T cell exhaustion from excess heat shock proteins, notably HSPA8. However, CD8 T cell cytotoxic functions improve post-treatment. In myeloid cells, anti-PD-1 therapy enhances antigen presentation and promotes a proinflammatory shift post-metastasis. Additionally, NUPR1 is linked to BM in LSCC, and NEAT1 is a potential metastatic cancer cell cycle participant. Our study provides insights into cancer heterogeneity and the impact of PD-1 immunotherapy on metastasis, aiding precise diagnosis and prognosis.

Assessment of Geostationary Satellite Cloud Effective Radius over East China with In Situ Aircraft Measurements - Qiuli Zhang; Chao Liu; Rong Zhang; Jing Yang; Junxia Li; Bo Li; Feng Lu; Yan Yin; Hongchun Jin (Journal of Meteorological Research, 2025)

Water competition among coexisting plants in rock-dominated habitats of subtropical karst desertification - Lulu Cai; Kangning Xiong; Ziqi Liu; Yuan Li; Dayun Zhu; Yating Mu; Yi Chen; Rong Zhou; Xiaoyu Yan (Agriculture, Ecosystems & Environment, 2025)

A multi-task model for mill load parameter prediction using physical information and domain adaptation: Validation with laboratory ball mill - Yiwen Liu; Gaowei Yan; Shuyi Xiao; Fang Wang; Rong Li; Yusong Pang (Minerals Engineering, 2025)

Accumulation of lipophilic and proteinophilic halogenated organic pollutants (HOPs) in the different types of feathers of laying hens - Xi Chen; Xiao-Jun Luo; Qun-Jie Feng; Yu Liu; Jun-Zhe Dai; Peng-Peng Chen; Pei-Xin Su; Qing-Rong Yang; Yan-Hong Zeng; Bi-Xian Mai (Journal of Hazardous Materials, 2025)

Petrogenesis and geodynamic implications of gabbroic diorites of the early Paleozoic Mijiashan ophiolite in the eastern North Qilian Orogenic Belt, NW China - Jiao-Long Zhao; Liang Liu; Qing-Yan Tang; Jin-Rong Wang; Zhen-Xi Yang; Pei-Qing Hu; Xin-Wei Zhai; Saniye Abdereyimu; Zi-Han Dang (Journal of Asian Earth Sciences, 2025)

Thermal comfort and urban microclimate response: A new thermal environment assessment model for waterfront spaces in historic ancient towns - Yan Wang; Xinrui Liu; Rong Xie; Jiajing Wang; Qiwei Dong; Wanxiang Yao; Dahu Lin (Energy and Buildings, 2025)

Construction of high-voltage aqueous Zn-MnO2 batteries based on polar small-molecule organic acid-induced MnO2/Mn2+ reactions - Ying Li; Nan Zhang; Jing-Yu Wang; Pengfei Wang; Zonglin Liu; Yan-Rong Zhu; Jie Shu; Ting-Feng Yi (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Radiocarbon constraints on North Indian deep ocean ventilation and deglacial carbon dioxide release - Sui Wan; Yan Du; Lanlan Zhang; Liang Yi; Haowen Dang; Xiang Su; Jianguo Liu; Yiping Yang; Haoyin Wang; Rong Xiang (Quaternary Science Reviews, 2025)

Rational screening of metal single-atom-doped ZSM-5 to promote ring-opening cracking of cycloalkanes to light olefins - Jiarong Lu; Qi Shen; Rong Fan; Guoliang Li; Yaqian Li; Xinyang Zhang; Hao Yan; Yibin Liu; Tao Liu; Xiaobo Chen (Fuel, 2025)

A NIR fluorescent probe based on carbamoyl oxime with high specificity for detecting ferrous ions in food and in vivo - Caiyun Liu; Tingyi Yan; Tingting Fu; Kun Wang; Xiaodi Rong; Xueting Liu; Yao Wang; Xinyu Cai; Wenlong Sheng; Baocun Zhu (Food Research International, 2025)

Design, synthesis and antifungal activity of novel pyrazole-amide-isothiazole derivatives as succinate dehydrogenase inhibitors - Ai-ling Bao; Xian-song Xie; De-yuan Wang; Zi-quan Deng; Yun Chen; Dan Liu; Wei-yi Li; Xiao-rong Tang; Wei Cheng; Ying-kun Yan (Food Chemistry, 2025)

A sandwich-structured anisotropic conductive film with robust interfacial reliability and conductivity for functional electrical interconnections - Yang Liu; Yan Pan; Zeyu Zheng; Hebin Zhang; Rong Sun; Pengli Zhu (Chemical Engineering Journal, 2025)

Revisiting bipolar membrane electrodialysis for the production of monoprotic organic acids with different p K a and Mw - Rong Zhou; Zhiguo Dong; Xixi Ma; Lili Xue; Jinxin Liu; Jinfeng He; Weiwei Li; Li Sun; Chuanrun Li; Haiyang Yan (Chemical Engineering Journal, 2025)

The key pathogenic factor GcSP2 of Geotrichum citri-aurantii plays an important role in disrupting citrus metabolism and immunity - Rong Liu; Haoxiang Zheng; Di Wang; Haijue Zhang; Yan Wu; Xue Li; Zhengfeng Liu; QingJun Kong; Xueyan Ren (Postharvest Biology and Technology, 2025)

Structurally diversified sesquiterpenoids from Chloranthus henryi and their neuroprotective activities on H2O2 damaged PC12 cells - Meng-Li He; Lian-Lian Xu; Yang Liu; Yan-Ping Gao; Yong-Ming Luo; Rong-Cai Yue; Fang-You Chen (Phytochemistry, 2025)

Preparation and performance evaluation of an efficient microbial dust suppressant for dust control in disturbed areas of blast piles in open-pit coal mines - Jie Chen; Haoran Wang; Yi He; Rong Liu; Chuanhui Zeng; Kunyu Yan; Junpeng Zhu (Journal of Environmental Management, 2025)

Electromagnetic field coupled vertical flow constructed wetlands for rural sewage treatment: Performance, microbial community characteristics and metabolic pathways - Xiuxiu Lu; Yan Wang; Yungen Liu; Xin Xue; Chuandong Fu; Liechao Xiong; Liping Peng; Silin Yang; Rong Ma (Journal of Environmental Management, 2025)

Turning coal hydrogenation liquefaction residue into high conductivity carbon black with magnesium citrate-assisted steam activation followed by high temperature treatment - Qian Meng; Huiping Sun; Yiyang Rong; Mengxue Tang; Yan Tan; Ting Liu; Zizhen Ma; Huawei Zhang (Fuel, 2025)

Efficient preparation of cycloamylose from potato starch using recombinant 4-α-glucanotransferase - Yan Huang; Rong Zhu; Jiehu Liu; Xueyi Qiao; Bo Xu; Lei Wang; Lingqia Su (Systems Microbiology and Biomanufacturing, 2025)

Evaluation of metagenomic next-generation sequencing (mNGS) combined with quantitative PCR: cutting-edge methods for rapid diagnosis of non-invasive fungal rhinosinusitis - Xiao Liu; Shaoqin Zhou; Rong Yan; Caifeng Xia; Ruoning Xue; Zhe Wan; Ruoyu Li; Sybren de Hoog; Sarah A. Ahmed; Quangui Wang; Yinggai Song (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Leaf Photosynthetic and Respiratory Thermal Acclimation in Terrestrial Plants in Response to Warming: A Global Synthesis - Ting Wu; David T. Tissue; Mingkai Jiang; Martijn Slot; Kristine Y. Crous; Junfeng Yuan; Juxiu Liu; Shaofei Jin; Chenxi Wu; Yan Deng; Chao Huang; Fuxi Shi; et al. (Global Change Biology, 2025)
Leaf photosynthesis and respiration are two of the largest carbon fluxes between the atmosphere and biosphere. Although experiments examining the warming effects on photosynthetic and respiratory thermal acclimation have been widely conducted, the sensitivity of various ecosystem and vegetation types to warming remains uncertain. Here we conducted a meta‐analysis on experimental observations of thermal acclimation worldwide. We found that the optimum temperature for photosynthetic rate ( T opt ) and the maximum rate of carboxylation of Rubisco ( T opt V) in tropical forest plants increased by 0.51°C and 2.12°C per 1°C of warming, respectively. Similarly, T opt and the optimum temperature for maximum electron transport rate for RuBP regeneration ( T opt J) in temperate forest plants increased by 0.91°C and 0.15°C per 1°C of warming, respectively. However, reduced photosynthetic rates at optimum temperature ( A opt ) were observed in tropical forest (17.2%) and grassland (16.5%) plants, indicating that they exhibited limited photosynthetic thermal acclimation to warming. Warming reduced respiration rate ( R 25 ) in boreal forest plants by 6.2%, suggesting that respiration can acclimate to warming. Photosynthesis and respiration of broadleaved deciduous trees may adapt to warming, as indicated by higher A opt (7.5%) and T opt (1.08°C per 1°C of warming), but lower R 25 (7.7%). We found limited photosynthetic thermal acclimation in needleleaved evergreen trees (−14.1%) and herbs (−16.3%), both associated with reduced A opt . Respiration of needleleaved deciduous trees acclimated to warming (reduced R 25 and temperature sensitivity of respiration (Q 10 )); however, broadleaved evergreen trees did not acclimate (increased R 25 ). Plants in grasslands and herbaceous species displayed the weakest photosynthetic acclimation to warming, primarily due to the significant reductions in A opt . Our global synthesis provides a comprehensive analysis of the divergent effects of warming on thermal acclimation across ecosystem and vegetation types, and provides a framework for modeling responses of vegetation carbon cycling to warming.

Pollution status and assessment of seven heavy metals in the seawater and sediments of Hangzhou Bay, China - Rong Zhu; Yan-Yan Zeng; Li-Min Liu; Lu Yin; Kai-Ping Xu; Wei-Feng Chen; Shang-Chun Li; Xiao-Feng Zhou (Marine Pollution Bulletin, 2024)

Effects of nitrite exposure on the oxidative stress, immune response and intestine microbiota of Procambarus clarkii - Dan-Dan Bian; Yan-Xia Shi; Xi-Rong Zhu; Xiao-Li Sun; Xuan Xu; Lu Ding; Dai-Zhen Zhang; Qiu-Ning Liu; Bo-Ping Tang; Bao-Jian Zhu (Aquaculture, 2024)

Unveiling spatiotemporal distribution, partitioning, and transport mechanisms of tire additives and their transformation products in a highly urbanized estuarine region - Hai-Yan Zhang; Yue-Hong Liu; Li-Ni Wei; Rui-Qi Zhu; Jian-Liang Zhao; Shan Liu; Xiang-Rong Xu; Guang-Guo Ying (Science of The Total Environment, 2024)

β-Caryophyllene oxide inhibits lysine acetylation of histones in Fusarium proliferatum to block ribosomal biosynthesis and function - Hong-Xin Liao; Jing Yang; Jin-Rui Wen; Hong-Yan Nie; Jun Zhao; Fu-Rong Xu; Xiao-Yun Liu; Xian Dong (Pesticide Biochemistry and Physiology, 2024)

Epidemiological and genomic analysis revealed the significant role of flies in dissemination of carbapenem-resistant Enterobacteriaceae (CRE) in China - Hongwei Zhou; Hanyu Wang; Kaichao Chen; Miaomiao Xie; Zelin Yan; Yanyan Zhang; Yuchen Wu; Dejun Liu; Juan Wang; Ning Dong; Chang Cai; Yongning Wu; et al. (Journal of Hazardous Materials, 2024)

Optimizing interactions for efficient hydrogen evolution reaction by incorporating rhenium nanoparticles on defect-rich carbon - Yi-Sha Ba; Wen Lei; Xin Du; Yan-Xin Duan; Rong-Chao Cui; Zhong-Yi Liu; Xin-Zheng Yue (Fuel, 2024)

Quality improvement of threadfin bream (Nemipterus virgatus) surimi-gel using soy protein as a natural food additive - Yi-Li Gao; Asami Yoshida; Jin-Yang Liu; Jing Yuan; Shinnosuke Maeda; Youjun Wang; Yan-Rong Jiang; Xiao-Mi Sun; Chao-Ping Chen; Yajun Wang; Tetsuhiko Okajima; Kiyoshi Osatomi (Food Chemistry, 2024)

Electrodialysis with ultrafiltration membrane for efficient isolation of oxymatrine from simulated eluent of traditional Chinese medicine - Zhiguo Dong; Rong Zhou; Zengqiang Wei; Yiwei Dong; Li Sun; Xixi Ma; Wenlong Liu; Qiuhua Li; Jinfeng He; Chuanrun Li; Haiyang Yan (Desalination, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Correction: A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Genomic characteristics of a novel non-segmented double-stranded RNA mycovirus from the fungus Nigrospora oryzae - Ya Rong Wang; Jie Zhong; Tian Bo Liu; Yan Song Xiao (Archives of Virology, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Exploring the variations in molecular characteristics of dissolved organic matter driven by aquaculture types - Li-Ping Li; Xin-Yi Jiao; Shuang Peng; Dong-Bin Wei; Yan-Chao Jin; Cai-Shan Wang; Ding Pan; Peng Liu; Xue-Rong Wang; Yu-Ping Tang; Dong Ren; Xin-Hui Liu (Water Research, 2024)

Degradation characteristics and effect mechanisms of estrogens during aerobic composting of chicken manure based on the orthogonal test - Ziwei Liang; Junhao Wu; De-Chun He; Yan Li; Yan-Qiu Liang; Jia-Wu Hu; Meng-Yao Zou; Jian-Feng Ning; Wang-Rong Liu (Journal of Environmental Management, 2024)

3D printing technologies in water Treatment: Applications, Challenges, and emerging trends - Yun-fei Zhang; Jin-ze Li; Yue Zou; Yan-lin Liu; Lei Li; Jian-hui Xu; Dan Li; Qiang-qiang Rong; Jian-ying Li; Yi-xin Geng; Jia-wei Lai (Chemical Engineering Journal, 2024)

Combined utilization of slag, fly ash, and polyacrylamide for sustainable saline soil improvement: a win-win strategy - Yang Zhao; Zheng Lu; Rong Zhang; Jie Liu; Changtao Hu; Abdollah Tabaroei; Jian Li; Tingzhou Yan; Hailin Yao (Bulletin of Engineering Geology and the Environment, 2024)

Construction of oxygen-doped g-C3N4/BiOCl (S-scheme) heterojunction: Efficient degradation of tetracycline in wastewater - Yuan Wei; Yu-Bing Liu; Chao Liu; Xin Li; Guang-Hong Zhao; Rong-Hui Liu; Hong-Yu Wang; Yan-Yan Jiang; Yu-Lan Zhang; Yu-Hui Gao; Gao-Feng Shi; Guo-Ying Wang (Journal of Environmental Chemical Engineering, 2024)

Ru0.7Cu0.3/W18O49 Schottky junction for visible-light-driven hydrogen generation from ammonia borane hydrolysis - Shu-Bin Li; Wei-Yang Long; Chuan-Qi Li; Yan-Xin Duan; Rong-Chao Cui; Zhong-Yi Liu; Xin-Zheng Yue (Fuel, 2024)

Novel pH- and thermal-responsive oleogel capsules: Featuring an oleogel core and ultrathin calcium-alginate shell - Yumeng Shi; Jiayi Tang; Wenyu Yan; Yan Liu; Yuchun Liu; Huan Chen; Cheng Yang; Chunhuan Liu; Rong Liang (Food Chemistry, 2024)

N, S-carbon quantum dots as inhibitor in pickling process of heat exchangers for enhanced performance in multi-stage flash seawater desalination - Bochuan Tan; Yan Liu; Haiqin Ren; Zhili Gong; Xin Li; Wenpo Li; Lei Guo; Rong Chen; Juxiang Wei; Qingwei Dai; Abeer A. AlObaid (Desalination, 2024)

Nomogram to Predict Good Neoangiogenesis After Indirect Revascularization Surgery in Patients with Moyamoya Disease: a Case–control Study - Kexin Yuan; Ke Wang; Haibin Zhang; Yunfan Zhou; Qiang Hao; Xun Ye; Xingju Liu; Qian Zhang; Yan Zhang; Rong Wang; Yuanli Zhao; Yahui Zhao (Translational Stroke Research, 2024)

Sulphur in apatite: a potential monitor of the magmatic redox state in the world-class gold fields of the North China Craton - Jia-Wei Liu; Lin Li; Sheng-Rong Li; M. Santosh; Mao-Wen Yuan; Masroor Alam; Shun-Feng Yan (International Geology Review, 2024)

Location-dependent occurrence and distribution of metal-based nanoparticles in bay environments - Siying Ying; Ziyi Liu; Yongrong Hu; Rong Peng; Xiaoshan Zhu; Shuofei Dong; Dong Yan; Yuxiong Huang (Journal of Hazardous Materials, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Argon non-thermal plasma treatment promotes the development of rice (Oryza sativa L.) in saline alkali environments - Kai Liu; Yan-Jiang Feng; Jun-Xiang Guo; Gui-Ling Wang; Li-Li Shan; Shi-Wei Gao; Qing Liu; Hu-Nan Sun; Xi-Yu Li; Xing-Rong Sun; Jing-Yang Bian; Taeho Kwon (Protoplasma, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Experimental Study on Acoustic Emission Properties and Damage Characteristics of Basalt Exposed to High Temperature Treatment - Wenzhao Chen; Rong Hu; Xiqi Liu; Gang Wang; Bingwen Gong; Yan Chang; Heng Deng; Chunming Qi (Geotechnical and Geological Engineering, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Mass cytometry revealed the circulating immune cell landscape across different Suzuki stages of Moyamoya disease - Chenglong Liu; Peicong Ge; Bojian Zhang; Liujia Chan; Yuheng Pang; Chuming Tao; Junsheng Li; Qiheng He; Wei Liu; Siqi Mou; Zhiyao Zheng; Zhikang Zhao; et al. (Immunologic Research, 2024)
Moyamoya disease (MMD) is a cerebrovascular disorder marked by progressive arterial narrowing, categorized into six stages known as Suzuki stages based on angiographic features. Growing evidence indicates a pivotal role of systemic immune and inflammatory responses in the initiation and advancement of MMD. This study employs high-dimensional mass cytometry to reveal the immunophenotypic characteristics of peripheral blood immune cells (PBMCs) at various Suzuki stages, offering insights into the progression of MMD. PBMC samples from eight patients with early-stage MMD (Suzuki stages II and III) and eight patients with later-stage MMD (Suzuki stages IV, V, and VI) were analyzed using high-dimensional mass cytometry to evaluate the frequency and phenotype of immune cell subtypes. We identified 15 cell clusters and found that the immunological features of early-stage MMD and later-stage MMD are composed of cluster variations. In this study, we confirmed that, compared to later-stage MMD, the early-stage MMD group exhibits an increase in non-classical monocytes. As the Suzuki stage level increases, the proportions of plasmacytoid DCs and monocyte-derived DCs decrease. Furthermore, T cells, monocytes, DCs, and PMN-MDSCs in the early-stage MMD group show activation of the canonical NF-κB signaling pathway. We summarized and compared the similarities and differences between early-stage MMD patients and later-stage MMD patients. There is a potential role of circulating immune dysfunction and inflammatory responses in the onset and development of MMD.

Interior decorative volatile organic compounds exposure induces sleep disorders through aberrant branched chain amino acid transaminase 2 mediated glutamatergic signaling resulting from a neuroinflammatory cascade - Jie Zheng; Mengqi Wu; Yaxian Pang; Qingping Liu; Yan Liu; Xiaoting Jin; Jinglong Tang; Lei Bao; Yujie Niu; Yuxin Zheng; Rong Zhang (Science of The Total Environment, 2024)

Biocontrol performance of a novel Bacillus velezensis L33a on tomato gray mold and its complete genome sequence analysis - Lixinyu Sun; Yu Chen; Shiyu Liu; Xiaogang Ou; Yangyang Wang; Zhengwu Zhao; Rong Tang; Yingzhe Yan; Xinyue Zeng; Shun Feng; Tao Zhang; Zhengguo Li; et al. (Postharvest Biology and Technology, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

Path tracking control for brake-steering tracked vehicles based on an improved pure pursuit algorithm - Chenming Hu; Yu Ru; Xianzhe Li; Shuping Fang; Hongping Zhou; Xianghai Yan; Mengnan Liu; Rong Xie (Biosystems Engineering, 2024)

ZnO nanorod coatings attenuate antibiotic resistance genes (ARGs) on their surface biofilms in estuarine environment - Xing-pan Guo; Rong-rong Sha; Yu-cen Wang; Jia Yan; Bo Peng; Zuo-shun Niu; Wen-liang Liu; Xin Li; Yi Yang (Journal of Environmental Chemical Engineering, 2024)

Biomineralization-inspired porous calcium carbonate microspheres as a controlled release system of herbicides/pesticides - Yaoxun Zeng; Xinyi Li; Fangzheng Chen; Huiling Ye; Keyi Rong; Zhili Ran; Binhong Liu; Zhenxing Pan; Xiuxian Xie; Junze Tang; Xujie Liu; Yan He (Journal of Environmental Chemical Engineering, 2024)

High mineralization efficiency of chlorobenzene oxidation using a metal-interaction strengthening MnCoOx catalyst derived from ZIF-67 - Shuangshuang Fu; Dongjie Yan; Dan Tao; Ning Yang; Kaixian Liu; Yifan Rong; Lu Li; Chi He (Fuel, 2024)

Controllable fabrication of alginate-based floating beads with core-shell architecture - Chunhuan Liu; Yumeng Shi; Yuchun Liu; Yan Liu; Chenjing Yang; Huan Chen; Cheng Yang; Rong Liang (Food Hydrocolloids, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

CYTOR-NFAT1 feedback loop regulates epithelial-mesenchymal transition of retinal pigment epithelial cells - Rong Zhang; Lin Wang; Yang Li; Yan Liu; Kui Dong; Yajing Pei; Junmei Zhao; Gang Liu; Jing Li; Xiaodan Zhang; Tong Cui; Yan Gao; et al. (Human Cell, 2024)

Comparative assessment of leaf photosynthetic capacity datasets for estimating terrestrial gross primary productivity - Mingzhu Xu; Jing M. Chen; Yihong Liu; Rong Wang; Rong Shang; Jiye Leng; Lei Shu; Jane Liu; Ronggao Liu; Yang Liu; Rongjuan Yang; Yulin Yan (Science of The Total Environment, 2024)

In vitro degradation and dual responsively antibacterial zeolitic imidazolate frameworks-8@Rhein composite coating on magnesium alloy - Chen-Hui Duan; Kui Xue; Lan-Yue Cui; Xue-Wen Jiang; Yan-Yu Zhang; Cheng-Bao Liu; Shuo-Qi Li; Fen Zhang; Rong-Chang Zeng (Chemical Engineering Journal, 2024)

LSTM-based deformation forecasting for additional stress estimation of existing tunnel structure induced by adjacent shield tunneling - Xiao-Wei Ye; Si-Yuan Ma; Zhi-Xiong Liu; Yan-Bo Chen; Ci-Rong Lu; Yue-Jun Song; Xiao-Jun Li; Li-An Zhao (Tunnelling and Underground Space Technology, 2024)

Multi-source unsupervised domain adaptive mill load forecasting method based on deep learning and fusion features - Yiwen Liu; Gaowei Yan; Rong Li; Shuyi Xiao; Mifeng Ren; Lan Cheng (Minerals Engineering, 2024)

Cultivation mode of Saccharina japonica impacts planktonic and epiphytic microbiomes - Yongwei Yan; Shanshan Wang; Shaojun Pang; Kuimei Liu; Lirong Chang; Xiaojun Rong; Jie Li (Algal Research, 2024)

Modulation of plasmacytoid dendritic cell and CD4+ T cell differentiation accompanied by upregulation of the cholinergic anti-inflammatory pathway induced by enterovirus 71 - Li Li; Rong-Wei Huang; Xiao-Ning Liu; Xiao-Yi Xiang; Yuan-Tao Zhou; Xing-Xing Feng; Lv-Yuan Tao; Jia Yu; Qin Yi; Yan-Chun Wang; Xiao-Mei Liu (Archives of Virology, 2024)

Hydrodynamic characteristics of frustum-type depressor for sampling midwater trawl - Zhiqiang Liu; Fuxiang Hu; Rong Wan; Yucheng Wang; Shaojian Guo; Hao Yan; Cheng Zhou (Ocean Engineering, 2024)

Study by means of 1H nuclear magnetic resonance of the oxidation process in high oleic sunflower oil and palm oil during deep-frying of fish cakes - Xiaoyu Luo; Benlun Hu; Caihua Jia; Ru Liu; Jianhua Rong; Siming Zhao; Meng Niu; Yan Xu; Tao Yin; Juan You (Food Research International, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Uranium speciation and distribution on the surface of Shewanella putrefaciens in the presence of inorganic phosphate and zero-valent iron under anaerobic conditions - Guo-Xiu Xuan; Guo-Hao Zhang; Wen-Cai Cheng; Chun-Yan Ma; Qing-Rong Li; En-Tong Liu; Wen-Ge He; Fa-Qin Dong; Xiao-An Li; Zheng-Guo Chen; Xiao-Qin Nie (Science of The Total Environment, 2024)

Suspended particulate matter <2.5 μm (SPM2.5) in shallow lakes: Sedimentation resistance and bioavailable phosphorus enrichment after sediment resuspension - Zhaona Zhou; Rong Yan; Xiao Liu; Ziying Xu; Jin Zhang; Qitao Yi (Science of The Total Environment, 2024)

Associations of legacy perfluoroalkyl and polyfluoroalkyl substances, alternatives, and isomers with gestational diabetes mellitus and glucose homeostasis among women conceiving through assisted reproduction in Shanghai, China - Dandan Mao; Guodong Ding; Zixia Wang; Jiuru Zhao; Hong Li; Xiaoning Lei; Jiaqi Zheng; Yan Zhang; Rong Shi; Tao Yuan; Zhiwei Liu; Yu Gao; et al. (Environmental Science and Pollution Research, 2024)

Interplanting leguminous shrubs boosts the trophic interactions of soil micro-food web in a karst grassland - Jiachen Wang; Jie Zhao; Rong Yang; Xin Liu; Xuyuan Zhang; Wei Zhang; Xiaoyong Chen; Wende Yan; Kelin Wang (Soil Biology and Biochemistry, 2024)

Enhancing the removal of chlorinated hydrocarbons from groundwater using a new BL5 microorganism with functional CS@ZVI materials - Zhiguo Chen; Wenqing Cao; Yan Li; Jingpeng Song; Yiyun Liu; Juncheng Liu; Rong Zhang; Rongxin Su; He Bai (Journal of Water Process Engineering, 2024)

An appropriate amount of straw replaced chemical fertilizers returning reduced net greenhouse gas emissions and improved net ecological economic benefits - Lian Zhang; Guoliang Jiang; Rusheng Xiao; Kun Hou; Xin Liu; Xinyu Liu; Pei Yuan; Feng Tian; Lichu Yin; Hongmei Zhu; Chang Tian; Lan Yang; et al. (Journal of Cleaner Production, 2024)

Untargeted metabolomics analysis of non-volatile metabolites and dynamic changes of antioxidant capacity in Douchi with edible mushroom by-products - Pei-Xiu Rong; Xiao-Qin He; Mutamed Ayyash; Yi Liu; Ding-Tao Wu; Fang Geng; Hua-Bin Li; Siew Bee Ng; Hong-Yan Liu; Ren-You Gan (Food Chemistry, 2024)

Exposure levels and determinants of placental polybrominated diphenyl ethers in Chinese pregnant women - Yijun Liu; Yan Xie; Yingkuan Tian; Juan Liao; Derong Fang; Linglu Wang; Rong Zeng; Shimin Xiong; Xingyan Liu; Qing Chen; Ya Zhang; Hongyu Yuan; et al. (Environmental Research, 2024)

NixSy/NF composites assembled by sulfidation of nickel foam (NF) for highly effective capture of iodine - Bo Qiao; Haiqing Yan; Chaonan Wang; Huiqin Yao; Zidan Cai; Keren Shi; Rong Liu; Shulan Ma (Chemical Engineering Journal, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

A near-infrared fluorescent probe for viscosity: Differentiating cancer cells from normal cells and dual-modal imaging in tumor mice - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Yongfei Li; Chun-Yan Li (Analytica Chimica Acta, 2024)

Phenolic and bisamide derivatives from Aglaia odorata and their biological activities - Xiaomeng Yang; Yan Yu; Panfeng Wu; Juan Liu; Yanan Li; Linlan Tao; Rong Tan; Xiaojiang Hao; Chunmao Yuan; Ping Yi (Natural Product Research, 2023)

Effect comparisons of different conditioners and microbial agents on the degradation of estrogens during dairy manure composting - Yan Li; Dong Zeng; Xiao-Lu Jiang; De-Chun He; Jia-Wu Hu; Zi-Wei Liang; Jia-Cheng Wang; Wang-Rong Liu (Chemosphere, 2023)

Investigation on the catalytic performance of magnetic copper ferrite nanoparticles in the catalytic hydroconversion of Hanglaiwan long flame coal - Yong Gao; Wen-Xian Qin; Jin-Jun Bai; Qi-Yang Zhu; Xia-Long Li; Guang-Hui Liu; Xian-Yong Wei; Yu-Hong Kang; Yan-Jun Li; Xiang-Rong Ma; Zhi-Min Zong (Fuel, 2023)

A novel active packaging film containing citronella oil: Preparation, characterization, antimicrobial activity and application in grape preservation - Weijie Zhao; Changcheng Li; Weijia Ma; Ruiwen He; Yan Rong; Shovra Sarker; Qi Liu; Fang Tian (Food Packaging and Shelf Life, 2023)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

Efficacy of pterostilbene suppression on Aspergillus flavus growth, aflatoxin B1 biosynthesis and potential mechanisms - Yong-Mei Hu; Yi-Rong Wang; Wen-Bin Zhao; Yan Yan Ding; Zheng-Rong Wu; Guang-Han Wang; Peng Deng; Shao-Yong Zhang; Jun-Xia An; Zhi-Jun Zhang; Xiong-Fei Luo; Ying-Qian Liu (International Journal of Food Microbiology, 2023)

Hydrogel-based intelligent greenhouse films for simultaneous fogging prevention and indoor environmental monitoring - Honglang Lu; Huanxiong Liang; Jianle Liu; Hui Zhou; Menghan Pi; Min Li; Bin Yan; Wei Li; Wei Cui; Rong Ran (Chemical Engineering Journal, 2023)

Legume-based crop diversification reinforces soil health and carbon storage driven by microbial biomass and aggregates - Zhengjun Yan; Jie Zhou; Chunyan Liu; Rong Jia; Kevin Z. Mganga; Lei Yang; Yadong Yang; Leanne Peixoto; Huadong Zang; Zhaohai Zeng (Soil and Tillage Research, 2023)

Cardiovascular effects of wearing respirators against particulate matter: A randomized crossover trial - Xin Meng; Meilin Yan; Meijie Jiang; Xueling Meng; Liang Qi; Xinyan Hu; Ruiwei Xu; Yunxiu Shi; Weiju Li; Shiyi Chen; Tong Zhu; Jing Deng; et al. (Science of The Total Environment, 2023)

Lack of the CCT domain changes the ability of mango MiCOL14A to resist salt and drought stress in Arabidopsis - Shu-Quan Chen; Cong Luo; Yuan Liu; Rong-Zhen Liang; Xing Huang; Ting-Ting Lu; Yi-Hang Guo; Ruo-Yan Li; Chu-Ting Huang; Zhuo Wang; Xin-Hua He (Plant Science, 2023)

Pogocablenes A-O, fifteen undescribed sesquiterpenoids with structural diversity from Pogostemon cablin - Shu-Yi Li; Yu-Mei Feng; Yan Zhou; Cai-Cen Liao; Lu Su; Dan Liu; Hong-Mei Li; Rong-Tao Li (Phytochemistry, 2023)

Tracing global N2O emission mitigation strategies through trade networks - Kemeng Liu; Rong Ma; Kejia Yan; Bo Zhang; Simin Xu; Cuiyang Feng (Journal of Environmental Management, 2023)

Balanced phosphorus fertilization enhances soil bacterial network complexity to maintain multifunctionality and plant production in dryland agricultural systems - Lei Liu; Rong Yan; Li Zhu; Yu Yang; Zhiyuan Gao; Wenjie Yang; Jinshan Liu (Agriculture, Ecosystems & Environment, 2023)

The early Late Triassic Yumen mafic rocks in the eastern Tethyan Himalaya: A record of the progressive opening of the Yarlung Zangbo Neo-Tethyan Ocean - Wei-Liang Liu; Zhong-Xi Xia; Yun Zhong; Chris Yakymchuk; Zhou-Rong Cai; He Xiao; Xing Liao; Chi Yan; Ru-Xin Ding; Jin-Nan Liu (Lithos, 2023)

Magma process of the ore-forming gabbrodiorite porphyry of the Meishan iron deposit, eastern China: Insights from the phenocrysts chemistry - Wen-Hao Liu; Man-Rong Jiang; Yan Xia; Xiao-Jun Zhang (Journal of Geochemical Exploration, 2023)

The global burden of schizophrenia and the impact of urbanization during 1990–2019: An analysis of the global burden of disease study 2019 - Xuanxuan Li; Ning Wei; Jian Song; Jintao Liu; Jiajun Yuan; Rong Song; Li Liu; Lu Mei; Shuangshuang Yan; Yudong Wu; Rubing Pan; Weizhuo Yi; et al. (Environmental Research, 2023)

Solvent-freely polymerizing catechol and paraformaldehyde to nitrogen-rich carbon for high-volumetric-performance supercapacitor - Yushuai Yao; Rong Zhou; Yi Yu; Jian Chen; Cheng Du; Yan Zhang; Tao Long; Liu Wan; Qiuyue Wang; Mingjiang Xie (Chemical Engineering Journal, 2023)

Spautin-1 Protects Against Mild TBI-Induced Anxiety-Like Behavior in Mice via Immunologically Silent Apoptosis - Hui-Tao Miao; Rong-Xin Song; Yue Xin; Lu-Ying Wang; Jin-Meng Lv; Na-Na Liu; Zhi-You Wu; Wei Zhang; Yan Li; Dong-Xue Zhang; Li-Min Zhang (NeuroMolecular Medicine, 2023)

Hyperglycemia symptom amelioration by Ascophyllum nodosum polysaccharides in mice with type 2 diabetes - Ligen Chen; Liang Shen; Lingyun Zhu; Fengwei Li; Xiaodong Ge; Xiujuan Xia; Hongwei Yan; Tingting Liu; Wei Xu; Rong Shao (Algal Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Emission of volatile organic compounds from landfill working surfaces: Formation potential of ozone and secondary organic aerosols - Silan Zhao; Rong Li; Shengwei Wang; Yanqing Liu; Wenjing Lu; Yan Zhao (Science of The Total Environment, 2023)

Sodium butyrate induces ferroptosis in endometrial cancer cells via the RBM3/SLC7A11 axis - Ziwei Wang; Wan Shu; Rong Zhao; Yan Liu; Hongbo Wang (Apoptosis, 2023)

Association of climatic variables with risk of transmission of influenza in Guangzhou, China, 2005–2021 - Rong Zhang; Ka Yan Lai; Wenhui Liu; Yanhui Liu; Wenfeng Cai; Chris Webster; Lei Luo; Chinmoy Sarkar (International Journal of Hygiene and Environmental Health, 2023)

Characterization of airborne microplastics at different workplaces of the poly(ethylene:propylene:diene) (EPDM) rubber industry - Xiaoni Sun; Rong Song; Jintao Liu; Shuangshuang Yan; Yuxuan Li; Xiaoyu Jin; Yunfeng Liang; Yudong Wu; Lu Mei; Rubing Pan; Weizhuo Yi; Jian Song; et al. (Environmental Science and Pollution Research, 2023)

SRSF1 is crucial for male meiosis through alternative splicing during homologous pairing and synapsis in mice - Longjie Sun; Juan Chen; Rong Ye; Zheng Lv; Xuexue Chen; Xiaomei Xie; Yuheng Li; Chaofan Wang; Pengbo Lv; Lu Yan; Shuang Tian; Xiaohong Yao; et al. (Science Bulletin, 2023)

Differential Diagnosis of DCIS and Fibroadenoma Based on Ultrasound Images: a Difference-Based Self-Supervised Approach - Jin Yin; Jia-Jun Qiu; Jing-Yan Liu; Yi-Yue Li; Qi-Cheng Lao; Xiao-Rong Zhong; Mengling Feng; Hao Du; Shao-Liang Peng; Yu-Lan Peng (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Flooding duration affects the temperature sensitivity of soil extracellular enzyme activities in a lakeshore wetland in Poyang Lake, China - Xingyun Huang; Kexin Wang; Xiuting Wen; Jie Liu; Yan Zhang; Jun Rong; Ming Nie; Chun Fu; Bofu Zheng; Zhifen Yuan; Leiqiang Gong; Huiying Zhan; et al. (Science of The Total Environment, 2023)

Abundant bacterial subcommunity is structured by a stochastic process in an agricultural system with P fertilizer inputs - Lei Liu; Li Zhu; Rong Yan; Yu Yang; Jonathan M. Adams; Jinshan Liu (Science of The Total Environment, 2023)

Sunshine duration and risks of schizophrenia hospitalizations in main urban area: Do built environments modify the association? - Li Liu; Qing Wu; Xuanxuan Li; Rong Song; Ning Wei; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

Overexpression of Sedum SpHMA2, SpHMA3 and SpNramp6 in Brassica napus increases multiple heavy metals accumulation for phytoextraction - Zi Yang; Hai-Tao Wu; Hao Yang; Wan-Di Chen; Jia-Lan Liu; Fan Yang; Li Tai; Bin-Bin Li; Bo Yuan; Wen-Ting Liu; Yan-Feng Zhang; Yan-Rong Luo; et al. (Journal of Hazardous Materials, 2023)

Mesoporous zeolite Beta supported Ni nanoparticles for the catalytic hydroconversion of extraction portion from Jinjitan subbituminous coal to cycloalkanes - Juan Gao; Xian-Yong Wei; Yu-Hong Kang; Xiao-Qi Zhang; Ai-Min Wang; Xia-Long Li; Yong Gao; Guang-Hui Liu; Tao Chen; Yan-Jun Li; Xiang-Rong Ma; Jin-Jun Bai; et al. (Fuel, 2023)

DNA damage and up-regulation of PARP-1 induced by columbin in vitro and in vivo - Yufen Liao; Xin Wang; Guangyun Ran; Shiyu Zhang; Chutian Wu; Rong Tan; Ying Liu; Yan He; Ting Liu; Zhongxiu Wu; Ying Peng; Weiwei Li; et al. (Toxicology Letters, 2023)

Regulating the reaction pathway of nZVI to improve the decontamination performance through magnetic spatial confinement effect - Hai-Yuan Chi; Xiao-Xia Zhou; Min-Rong Wu; Wan-yu Shan; Jing-fu Liu; Jin-quan Wan; Bing Yan; Rui Liu (Journal of Hazardous Materials, 2023)

Exploring the paleoclimatic influence on the physico-mechanical properties of a loess-paleosol sequence in the sandy loess belt of China - Rong Liu; Dapeng Yue; Jingbo Zhao; Hao Shi; Xiaoning Wang; Yan Zhao; Yuzhe Yang (CATENA, 2023)

Retraction Note: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2023)

Study of coexisting upstream solitary wave packet and downstream wakes induced by Diaoyu Dao and its affiliated islands detected by satellite sun glitter - Lina Cai; Xiaoqi Jiang; Xiaojun Yan; Yan Bai; Jianqiang Liu; Menghan Yu; Rong Tang; Jingjing Jiang (Acta Oceanologica Sinica, 2023)

Influence mechanism of organic matter and low-molecular-weight organic acids on the interaction between minerals and PAHs - Longmiao Yuan; Yingqin Wu; Qiaohui Fan; Ping Li; Jianjun Liang; Yan hong Liu; Rong Ma; Ruijie Li; LeiPing Shi (Science of The Total Environment, 2023)

Aroma formation and transformation during sealed yellowing process of Pingyang yellow tea - Rong-Jian Dong; Xie-Huang Sheng; Qian-Tu Xie; Xiaolin Huang; Fujie Yan; Songbai Liu (Food Research International, 2023)

The impact of hazes on schizophrenia admissions and the synergistic effect with the combined atmospheric oxidation capacity in Hefei, China - Jiajun Yuan; Weiwei Chang; Zhenhai Yao; Liying Wen; Jintao Liu; Rubing Pan; Weizhuo Yi; Jian Song; Shuangshuang Yan; Xuanxuan Li; Li Liu; Ning Wei; et al. (Environmental Research, 2023)

Spinal cord astrocyte P2X7Rs mediate the inhibitory effect of electroacupuncture on visceral hypersensitivity of rat with irritable bowel syndrome - Zhi-jun Weng; Shi-xiu Hu; Fang Zhang; Zhi-ying Zhang; Yun Zhou; Min Zhao; Yan Huang; Yu-hu Xin; Huan-gan Wu; Hui-rong Liu (Purinergic Signalling, 2023)

Erythropoietin promotes energy metabolism to improve LPS-induced injury in HK-2 cells via SIRT1/PGC1-α pathway - Kan Li; Li Gao; Sen Zhou; Yan-Rong Ma; Xiao Xiao; Qian Jiang; Zhi-Hong Kang; Ming-Long Liu; Tian-Xi Liu (Molecular and Cellular Biochemistry, 2023)

Advances in post-operative prognostic models for hepatocellular carcinoma - Ziqin He; Xiaomin She; Ziyu Liu; Xing Gao; Lu Lu; Julu Huang; Cheng Lu; Yan Lin; Rong Liang; Jiazhou Ye (Journal of Zhejiang University-SCIENCE B, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

A near-infrared fluorescent probe for monitoring abnormal mitochondrial viscosity in cancer and fatty-liver mice model - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Dong-Hua Chen; Chun-Yan Li (Analytica Chimica Acta, 2023)

Exposure to polychlorinated biphenyls (PCBs) affects the histology and antioxidant capability of the clam Cyclina sinensis - Meimei Liu; Sishao Fan; Zhichao Rong; Hao Qiu; Susu Yan; Hongwei Ni; Zhiguo Dong (Frontiers in Marine Science, 2023)
Polychlorinated biphenyls (PCBs) are environmentally persistent and highly toxic organochlorine compounds that may cause toxic effects on aquatic animals. In this study we assess the toxic effect of PCBs on a bivalve used in aquaculture, the clam Cyclina sinensis . To this end, individuals of C. sinensis were exposed for 72 h at two PCB concentrations (1 ng/L and 10 ng/L) and control (absence of PCBs). At the end of the exposure, the hemolymph, hepatopancreas, and gills samples of C. sinensis were harvested for analysis of the enzyme activity and histology. The results showed that acute PCBs exposure decreased the survival rate of C. sinensis compared to the control. Acute PCBs exposure up-regulated the enzymatic activity of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px) and the content of malondialdehyde (MDA) in the hemolymph of C. sinensis , while down-regulated the non-specific enzymatic activity of alkaline phosphatase (AKP). For the hepatopancreas, 1 ng/L PCBs exposure up-regulated the enzymatic activity of SOD while down-regulated the enzymatic activity of CAT of C. sinensis . In the gill, the enzymatic activity of CAT decreased significantly and the MDA content increased of C. sinensis after 10 ng/L PCBs exposure. Moreover, histological observations showed that acute exposure to PCBs caused loss of gill filaments and lateral cilia and shortening of their length, in the studied organism. The present study will provide valuable reference data for marine shellfish aquaculture and toxicology research.

Divergence of epibacterial community assemblage correlates with malformation disease severity in Saccharina japonica seedlings - Yongwei Yan; Shanshan Wang; Kuimei Liu; Zhaolan Mo; Huichao Yang; Xiaojun Rong; Jie Li (Frontiers in Marine Science, 2023)
Malformation disease (MD) is one of the major constraints in the mariculture of the commercially important seaweed Saccharina japonica , which can cause severe losses of the kelp seedlings in the production process. However, the pathogenesis of MD remains largely undetermined. In this study, using cultivation experiments under laboratory conditions, MD severity was estimated for the young sporophytes of S. japonica , which were separately cultivated under different treatment conditions, including light intensity, duration of light exposure, and maturity level of the parent kelp. The associations between MD severity and epibacterial community divergence and assembly patterns were characterized. Higher MD severity significantly correlated with longer light exposure, and with both unmatured and overmatured parent kelp. The bacterial classes γ-Proteobacteria and α-Proteobacteria dominated all samples, but different MD severities were associated with different epibacterial communities. Comparisons of predicted functions for epibacterial communities revealed that longer light exposure led to a depletion in development and regeneration, while overmatured parent kelp resulted in a depletion in glycan biosynthesis and metabolism. Functional comparisons of the epibacterial communities between normal and unmatured parent kelp-generated seedlings revealed significantly different categories related to metabolism, environmental information processing, cellular processes, drug resistance, and bacterial infection. The significantly different pathways between groups, notably those related to bacterial infection and cellular processes, were partly consistent with the differences in bacterial compositions. The assembly of epiphytic bacterial communities was predominately governed by deterministic processes, and less impact was determined when there was significantly higher MD severity except when using overmatured parent kelp. Co-occurrence networks of the epibacterial communities associated with higher MD severity contained fewer nodes and exhibited lower modularity, but had higher graph density and degrees compared with those of seedlings with lower MD severity, indicating more complicated interactions. Nesterenkonia , Glycocaulis , Halomonas , Pseudoalteromonas , Pseudomonas , Loktanella , and Cobetia were frequently determined keystone taxa in communities associated with higher MD severity. The present study enhances our understanding of the factors significantly associated with MD severity and the potential roles of epimicrobiome in determining the disease severity, which will be useful for disease management in the future.

Gonad transcriptome analysis reveals the differences in gene expression related to sex-biased and reproduction of clam Cyclina sinensis - Meimei Liu; Hongwei Ni; Zichao Rong; Zi Wang; Susu Yan; Xiaoting Liao; Zhiguo Dong (Frontiers in Marine Science, 2023)
Sexual differentiation and gonad development are important biological processes for bivalve species. The clam Cyclina sinensis is an important cultured marine bivalve widely distributed along with the coastal areas of China. However, the information related to sexual determination/differentiation and gonadal development of C. sinensis almost has no reported. To study the molecular mechanisms of its sexual determination/differentiation and gonadal development, transcriptome analysis was performed in the gonad of C. sinensis , and the potential biological functions of reproduction-related gene were also investigated in this study. The results showed that 1 013 and 427 genes were differentially expressed in the ovary and testis, respectively. KEGG enrichment analysis showed that the DEGs in the gonad were significantly clustered in progesterone-mediated oocyte maturation, cell cycle and oocyte meiosis. Further analysis showed that 23 genes were mainly involved in sex determination/differentiation, including Dmrt1 , Sox2/4/9 , Foxl2 , β-catenin and GATA-type zinc finger protein 1-like. Twenty key genes were mainly involved in the process of spermatogenesis, and five genes encode steroid biosynthesis and metabolism. Fifteen genes related to ovarian development were also identified in this study, such as Vitellogenin , MAM and LDL-receptor class A domain-containing protein 1 and Cell division cycle protein 20 homolog . Moreover, 50µg/L estradiol treatment significantly up-regulated the expression levels of CsVg in the ovary and hepatopancreas. These results highlight the genes involved in sexual determination/differentiation and gonadal development, which enhance our understanding for further studies of reproduction and breeding of C. sinensis and other marine bivalves.

Revealing microcystin-LR ecotoxicity to earthworm (Eisenia fetida) at the intestinal cell level - Xiang Liu; Jin-Cheng Ye; Fen Li; Rong-Jun Gao; Xiao-Xiao Wang; Ji-Liang Cheng; Bai-Lin Liu; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; et al. (Chemosphere, 2023)

Zinc finger protein 671 has a cancer-inhibiting function in colorectal carcinoma via the deactivation of Notch signaling - Yan Wang; Fen-rong Chen; Chong-cao Wei; Lin-lang Sun; Chen-yu Liu; Long-bao Yang; Xiao-yan Guo (Toxicology and Applied Pharmacology, 2023)

Short-term exposure to air pollution is an emerging but neglected risk factor for schizophrenia: A systematic review and meta-analysis - Rong Song; Li Liu; Ning Wei; Xuanxuan Li; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Lu Mei; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

Moderate physical activity against effects of short-term PM2.5 exposure on BP via myokines-induced inflammation - Mengqi Wu; Yaxian Pang; Meiyu Chen; Lipeng Li; Lina Yan; Jie Ning; Qingping Liu; Yaling Zhang; Tao Jiang; Aijuan Kang; Xiaoyan Huang; Wentao Hu; et al. (Science of The Total Environment, 2023)

Iridoids and sesquiterpenoids from Valeriana officinalis and their bioactivities - Dao-Qun Shi; Jia-Jin Liu; Yu-Mei Feng; Yan Zhou; Cai-Cen Liao; Dan Liu; Rong-Tao Li; Hong-Mei Li (Phytochemistry, 2023)

Mice kidney biometabolic process analysis after cantharidin exposure using widely-targeted metabolomics combined with network pharmacology - Tianmu He; Lijuan Xiong; Yixin Zhang; Rong Yan; Ming Yu; Meichen Liu; Liu Liu; Cancan Duan; Xiaofei Li; Jianyong Zhang (Food and Chemical Toxicology, 2023)

Exposure–response relationship between temperature, relative humidity, and varicella: a multicity study in South China - Yihan Li; Jialing Li; Zhihua Zhu; Weilin Zeng; Qi Zhu; Zuhua Rong; Jianxiong Hu; Xing Li; Guanhao He; Jianguo Zhao; Lihua Yin; Yi Quan; et al. (Environmental Science and Pollution Research, 2023)

The Improving of Cd2+ Adsorption Performance of Hydrochar Obtained from Corn Straw Waste with KOH Activation - Yan Shi; Heng Li; Yushi Rong; Li Bai; Mingshu Chi; Xiuling Xu; Chenglin Li; Hao Bai; Yue Liu (Water, Air, & Soil Pollution, 2022)

GDH promotes isoprenaline-induced cardiac hypertrophy by activating mTOR signaling via elevation of α-ketoglutarate level - Zhi-Rong Lin; Zhen-Zhen Li; Yan-Jun Cao; Wen-Jing Yu; Jian-Tao Ye; Pei-Qing Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Naturally-Occurring Antibodies Against Bim are Decreased in Alzheimer’s Disease and Attenuate AD-type Pathology in a Mouse Model - Jie-Ming Jian; Dong-Yu Fan; Ding-Yuan Tian; Yuan Cheng; Pu-Yang Sun; Cheng-Rong Tan; Gui-Hua Zeng; Chen-Yang He; Ye-Ran Wang; Jie Zhu; Xiu-Qing Yao; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2022)

Transmission of SARS-CoV-2 on Cold-Chain Food: Precautions Can Effectively Reduce the Risk - Meiyue Guo; Junfeng Yan; Yuan Hu; Lu Xu; Jinling Song; Kun Yuan; Xiangru Cheng; Sui Ma; Jie Liu; Xianbing Wu; Liegang Liu; Shuang Rong; et al. (Food and Environmental Virology, 2022)

Fast forward modeling of muon transmission tomography based on model voxelization ray energy loss projection - Rong-Qing Zhang; Zhen-Zhu Xi; Wei Liu; He Wang; Zi-Yan Yang (Applied Geophysics, 2022)

Development of Physiology Based Pharmacokinetic Model to Predict the Drug Interactions of Voriconazole and Venetoclax - Ji Dong; Shuai-bing Liu; Jony Md Rasheduzzaman; Chen-rong Huang; Li-yan Miao (Pharmaceutical Research, 2022)

Discovery of a cryptic species, Erysiphe salicina sp. nov., and reconstruction of the phylogeny of powdery mildews on Populus and Salix spp. - Jing Feng; Shu-Yan Liu; Uwe Braun; Susumu Takamatsu; Michael Bradshaw; Seyed Akbar Khodaparast; Timur S. Bulgakov; Guan-Xiu Guan; Feng-Yun Zhao; Shu-Rong Tang (Mycological Progress, 2022)

Renal tubule ectopic lipid deposition in diabetic kidney disease rat model and in vitro mechanism of leptin intervention - Shasha Liu; Jingjing Da; Jiali Yu; Rong Dong; Jing Yuan; Fuxun Yu; Yan Zha (Journal of Physiology and Biochemistry, 2022)

Quinolizidine alkaloids from the roots of Sophora flavescens - Jian-Chun Li; Zhi-Jun Zhang; Dan Liu; Ming-Yan Jiang; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2022)

Effects of Chemotherapy on Neuroinflammation, Neuronal Damage, Neurogenesis, and Behavioral Performance in Bone Marrow Transplantation Recipient Mice - Zhong-Yuan Yu; Man-Yu Xu; Zhi-Hao Liu; Gui-Hua Zeng; Huan Fan; Cheng-Rong Tan; Yun-Feng Tu; Xian-Le Bu; Yan-Jiang Wang (Neurotoxicity Research, 2022)

Effect of Fertilization Regimes and Seasonal Change on nosZ-Denitrifying Bacterial Community in a Double-Rice Paddy Field - Jiangwen Nie; Yong Zhou; Wei Yang; Shaoqiu Li; Haoxuan Li; Jianwei Wu; Chengwei Li; Xiaoyuan Yan; Rong Zhu; Bo Zhu; Zhangyong Liu (Journal of Soil Science and Plant Nutrition, 2022)

Genetic diversity of Lathyrus sp collected from different geographical regions - Md. Mosiur Rahman; Md. Ruhul Quddus; Md. Omar Ali; Rong Liu; Mengwei Li; Xin Yan; Guan Li; Yishan Ji; Md. Monoar Hossain; Chenyu Wang; Ashutosh Sarker; Tao Yang; et al. (Molecular Biology Reports, 2022)

The addition of sawdust reduced the emission of nitrous oxide in pig manure composting by altering the bacterial community structure and functions - Chao Liu; Jiao Yan; Qian Huang; Hongjun Liu; Cece Qiao; Rong Li; Biao Shen; Qirong Shen (Environmental Science and Pollution Research, 2022)

Molecular cloning of myosin chaperone uncoordinate-45B (UNC-45B) and its heat stress response in the muscle of Pacific bluefin tuna Thunnus orientalis - Yi-Li Gao; Asami Yoshida; Jin-Yang Liu; Uno Yamashita; Yan-Rong Jiang; Xiao-Mi Sun; Kazuya Shirota; Yasuhiko Shiina; Kiyoshi Osatomi (Fisheries Science, 2021)

Development and application of the Faba_bean_130K targeted next-generation sequencing SNP genotyping platform based on transcriptome sequencing - Chenyu Wang; Rong Liu; Yujiao Liu; Wanwei Hou; Xuejun Wang; Yamei Miao; Yuhua He; Yu Ma; Guan Li; Dong Wang; Yishan Ji; Hongyan Zhang; et al. (Theoretical and Applied Genetics, 2021)

Different leaf carbon, nitrogen, and phosphorus stoichiometry and carbon and nitrogen isotopes among peatland plants in northeastern China - Chong-Juan Chen; Xue-Yan Liu; Xian-Wei Wang; Chao-Chen Hu; Shi-Qi Xu; Rong Mao; Zhao-Jun Bu; Yun-Ting Fang; Keisuke Koba (Plant and Soil, 2021)

Anti-inflammatory steroids from the fruits of Artocarpus heterophyllus - Yun-Yao Liu; Ting Wang; Rong-Xiang Yang; Hao-Xuan Tang; Lei Qiang; Yan-Ping Liu (Natural Product Research, 2021)

Influencing factors and physiochemical changes of embryogenesis through in vitro isolated microspore culture in Brassica species - Yan-Qi Dong; Yu-Hong Gao; Te Zhao; Guang-Qian Ren; Yan-Li Liu; Bin Guan; Rong-Xian Jin; Fei Gao; Yan-Li Zhang; Xiu-Fang Tan; Hong-Cai Zhu; Yu-Hong Zhang; et al. (Biologia, 2021)

A stable QTL qSalt-A04-1 contributes to salt tolerance in the cotton seed germination stage - Qishen Gu; Huifeng Ke; Chenchen Liu; Xing Lv; Zhengwen Sun; Zhengwen Liu; Wei Rong; Jun Yang; Yan Zhang; Liqiang Wu; Guiyin Zhang; Xingfen Wang; et al. (Theoretical and Applied Genetics, 2021)

Efficient modeling of the gravity anomaly caused by a sedimentary basin with lateral variable density contrast and its application in basement relief estimation - Xu-Liang Feng; Sheng-Rong Liu; Hong-Yan Shen (Applied Geophysics, 2021)

Clinical study on empirical and diagnostic-driven (pre-emptive) therapy of voriconazole in severe aplastic anaemia patients with invasive fungal disease after intensive immunosuppressive therapy - Yuhong Wu; Li Yan; Huaquan Wang; Hong Liu; Limin Xing; Rong Fu; Zonghong Shao (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Effect of bFGF on fibroblasts derived from the golden snub-nosed monkey - Xin Liu; Hao Wei; Jing Yang; Jingjing Li; Pei Zhang; Yuli Li; Rong Hou; Jinlian Hua; Xingrong Yan; Baoguo Li (Primates, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Antidepressant Effect of Paeoniflorin Is Through Inhibiting Pyroptosis CASP-11/GSDMD Pathway - Dan-Dan Tian; Min Wang; An Liu; Mei-Rong Gao; Chen Qiu; Wen Yu; Wen-Ju Wang; Kun Zhang; Le Yang; Yan-Yan Jia; Chang-Bin Yang; Yu-Mei Wu (Molecular Neurobiology, 2021)

The secondary metabolite regulator, BbSmr1 , is a central regulator of conidiation via the BrlA‐AbaA‐WetA pathway in Beauveria bassiana - Jin‐Feng Chen; Yu Liu; Gui‐Rong Tang; Dan Jin; Xi Chen; Yan Pei; Yan‐Hua Fan (Environmental Microbiology, 2021)
Summary The filamentous fungus Beauveria bassiana , an insect fungal pathogen, is widely used for pest biocontrol. Aerial conidia are infectious propagules, and their yield and viability greatly affect the field application of this fungus; however, little is known about the molecular regulatory mechanism of the triggered conidiation. In the present study, we find that the secondary metabolite regulator BbSmr1 is involved in the regulation of asexual conidiation development and stress response in B. bassiana . A deficiency in Bbsmr1 results in a prominent fluffy‐like phenotype on solid medium, decreased conidial yield, accelerated conidial germination, as well as increased tolerance to H 2 O 2 stress and cell wall inhibitors. The deletion of Bbsmr1 also leads to thickened conidial cell walls and changed cell epitopes. Overexpressing either BbbrlA or BbabaA in the ∆Bbsmr1 strain can rescue the phenotypes of conidial development and stress response. BbSmr1 activates BbbrlA transcription by directly binding to the A4GA3 sequence of the BbbrlA promoter. BbBrlA in turn binds to the promoter of Bbsmr1 and negatively regulates the expression of Bbsmr1 . These results indicate that BbSmr1 positively regulates conidial development in B. bassiana by activating the central development pathway BrlA‐AbaA‐WetA and provides insights into the developmental regulatory mechanism of entomopathogenic fungi.

Risk of congenital heart disease due to exposure to common electrical appliances during early pregnancy: a case-control study - Doudou Zhao; Leqian Guo; Ruo Zhang; Qixia Zhu; Hongli Wang; Rong Liu; Hong Yan; Shaonong Dang (Environmental Science and Pollution Research, 2021)

Heavy metal concentrations and associated health risks in edible tissues of marine nekton from the outer Pearl River Estuary, South China Sea - Chang-Ping Yang; Yan Liu; Bin-Bin Shan; Jing Xu; Wei Yu; Dian-Rong Sun; Zai-Wang Zhang (Environmental Science and Pollution Research, 2021)

A Re-evaluation of the Taxonomy and Classification of the Type III Secretion System in a Pathogenic Bacterium Causing Soft Rot Disease of Pleurotus eryngii - Feng Xu; Hui Yan; Yu Liu; Shuang Zhao; Shuang Song; Tongtong Gu; Zhongjuan Song; Jianbo Xie; Chengbo Rong (Current Microbiology, 2021)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

The intestine of artificially bred larval turbot (Scophthalmus maximus) contains a stable core group of microbiota - Zheng Zhang; Yongxiang Yu; Yan Jiang; Yingeng Wang; Meijie Liao; Xiaojun Rong; Qian Liu (Archives of Microbiology, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

The Joubert Syndrome Gene arl13b is Critical for Early Cerebellar Development in Zebrafish - Jian Zhu; Han-Tsing Wang; Yu-Rong Chen; Ling-Ya Yan; Ying-Ying Han; Ling-Yan Liu; Ying Cao; Zhi-Zhi Liu; Hong A. Xu (Neuroscience Bulletin, 2020)
Joubert syndrome is characterized by unique malformation of the cerebellar vermis. More than thirty Joubert syndrome genes have been identified, including ARL13B . However, its role in cerebellar development remains unexplored. We found that knockdown or knockout of arl13b impaired balance and locomotion in zebrafish larvae. Granule cells were selectively reduced in the corpus cerebelli, a structure homologous to the mammalian vermis. Purkinje cell progenitors were also selectively disturbed dorsomedially. The expression of atoh1 and ptf1 , proneural genes of granule and Purkinje cells, respectively, were selectively down-regulated along the dorsal midline of the cerebellum. Moreover, wnt1 , which is transiently expressed early in cerebellar development, was selectively reduced. Intriguingly, activating Wnt signaling partially rescued the granule cell defects in arl13b mutants. These findings suggested that Arl13b is necessary for the early development of cerebellar granule and Purkinje cells. The arl13b -deficient zebrafish can serve as a model organism for studying Joubert syndrome.

Retraction Note to: Ambient air pollution and adverse birth outcomes: a systematic review and meta-analysis - Le-qian Guo; Yu Chen; Bai-bing Mi; Shao-nong Dang; Dou-dou Zhao; Rong Liu; Hong-li Wang; Hong Yan (Journal of Zhejiang University-SCIENCE B, 2020)

Down-regulation of lncRNA CASC9 aggravates sepsis-induced acute lung injury by regulating miR-195-5p/PDK4 axis - Huai-rong Wang; Xiu-yan Guo; Xin-yan Liu; Xuan Song (Inflammation Research, 2020)

Association between PM2.5 and mortality of stomach and colorectal cancer in Xi’an: a time-series study - Crystal Jane Ethan; Kingsley Katleho Mokoena; Yan Yu; Karabo Shale; Yameng Fan; Jie Rong; Feng Liu (Environmental Science and Pollution Research, 2020)

Molecular evolution of GII.P17-GII.17 norovirus associated with sporadic acute gastroenteritis cases during 2013–2018 in Zhoushan Islands, China - Can Chen; Bing Wu; Hui Zhang; Ke-Feng Li; Rong Liu; Hong-Ling Wang; Jian-Bo Yan (Virus Genes, 2020)

Integrated fate assessment of aromatic amines in aerobic sewage treatment plants - Lin Jun Zhou; Zhi Yi Rong; Wen Gu; De Ling Fan; Ji Ning Liu; Li Li Shi; Yan Hua Xu; Zhi Ying Liu (Environmental Monitoring and Assessment, 2020)
The fate and exposure of chemicals in sewage treatment plants (STPs) are major considerations in risk assessment and environmental regulation. The biodegradability and removal of seven aromatic amines were systematically evaluated using a three-tiered integrated method: a standard ready biodegradability test, an aerobic sewage treatment simulation method, and model prediction. In tier 1, the seven aromatic amines were not readily biodegraded after 28 days. In adapted aerobic active sludge, 4-isopropyl aniline, 2,4-diaminotoluene, and 4-nitroaniline among them exhibited the degradation half-life time less than 20 h, the other four aromatic amines exhibited persistent with degradation half-life of > 60 h. In tier 2 of the aerobic sewage treatment simulation testing, 2,4-diaminotoluene, 4-nitroaniline, and 4-isopropylaniline demonstrated moderately to high overall removal. Hydraulic retention time (HRT) affects the removal with the optimum HRT was determined to be 12 h to 24. 2,6-Dimethyl aniline, 2-chloro-4-nitroaniline, 2,6-diethylaniline, and 3,4-dichloroaniline were not removed during the test, indicting these four aromatic amines will enter surface water and hence pose a potential risk to aquatic ecology. Considering the lack of an STP model in China for regulation purposes, in tier 3, we developed a Chinese STP (aerobic) (abbreviated as C-STP(O)) model that reflects a universal scenario for China to predict the fate. The predicted degradation, volatilization, and absorption showed a close relationship to the physicochemical properties of the chemicals, and had same tendency with tier 2 simulation test. The prediction showed that biodegradation rather than absorption or volatilization was the main removal process of aromatic amines in aerobic STP. With the combination of modified kinetics test with C-STP (O) model, the chemical fate can be more accurately predicted than using only the readily biodegradation result.

SsHKT1;1 is coordinated with SsSOS1 and SsNHX1 to regulate Na+ homeostasis in Suaeda salsa under saline conditions - Wen-Ying Wang; Ya-Qi Liu; Hui-Rong Duan; Xiu-Xia Yin; Yan-Nong Cui; Wei-Wei Chai; Xin Song; Timothy J. Flowers; Suo-Min Wang (Plant and Soil, 2020)

Roles of PTBP1 in alternative splicing, glycolysis, and oncogensis - Wei Zhu; Bo-lun Zhou; Li-juan Rong; Li Ye; Hong-juan Xu; Yao Zhou; Xue-jun Yan; Wei-dong Liu; Bin Zhu; Lei Wang; Xing-jun Jiang; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2020)

Sky islands as foci for divergence of fig trees and their pollinators in southwest China - Jun‐Yin Deng; Rong‐Hua Fu; Stephen G. Compton; Mei Liu; Qin Wang; Chuan Yuan; Lu‐Shui Zhang; Yan Chen (Molecular Ecology, 2020)
The dynamics of populations and their divergence over time have shaped current levels of biodiversity and in the case of the “sky islands” of mountainous southwest (SW) China have resulted in an area of exceptional botanical diversity. Ficus tikoua is a prostrate fig tree subendemic to the area that displays unique intraspecific diversity, producing figs typical of different pollination modes in different parts of its range. By combining climate models, genetic variation in populations of the tree's obligate fig wasp pollinators and distributions of the different plant phenotypes, we examined how this unusual situation may have developed. We identified three genetically distinct groups of a single Ceratosolen pollinator species that have largely parapatric distributions. The complex topography of the region contributed to genetic divergence among the pollinators by facilitating geographical isolation and providing refugia. Migration along elevations in response to climate oscillations further enhanced genetic differentiation of the three pollinator groups. Their distributions loosely correspond to the distributions of the functionally significant morphological differences in the male figs of their host plants, but postglacial expansion of one group has not been matched by spread of its associated plant phenotype, possibly due to a major river barrier. The results highlight how interplay between the complex topography of the “sky island” complex and climate change has shaped intraspecies differentiation and relationships between the plant and its pollinator. Similar processes may explain the exceptional botanical diversity of SW China.

RETRACTED ARTICLE: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2020)

One bis-indole alkaloid-voacamine from Voacanga africana Stapf: biological activity evaluation of PTP1B in vitro utilizing enzymology method based on SPRi expriment - Yan-Qiu Wang; Hong-Xiang Li; Xiao-Chun Liu; Jin-Shuang Zhao; Rong-Qiang Liu; Wen-ying Huai; Wei-Jun Ding; Tian-E Zhang; Yun Deng (Natural Product Research, 2019)

Paramyxoviruses respiratory syncytial virus, parainfluenza virus, and human metapneumovirus infection in pediatric hospitalized patients and climate correlation in a subtropical region of southern China: a 7-year survey - Wen-Kuan Liu; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Li Zhang; Shu-Jun Gu; Rong Zhou; Qian Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

The complete chloroplast genome of the daimyo oak, Quercus dentata Thunb. - Hua-Lei Hu; Jing-Yu Zhang; Yu-Ping Li; Lu Xie; Dong-Bin Chen; Qun Li; Yan-Qun Liu; Shu-Rong Hui; Li Qin (Conservation Genetics Resources, 2019)

An integrated prevention strategy to address problems associated with continuous cropping of watermelon caused by Fusarium oxysporum - Fu-Yan Liu; Qiang Zhu; Hu-Rong Yang; Jun Zhou; Chuan-Chao Dai; Xing-Xiang Wang (European Journal of Plant Pathology, 2019)

Identification of cis-regulatory regions responsible for developmental and hormonal regulation of HbHMGS1 in transgenic Arabidopsis thaliana - Xiao-Xiao Gong; Bing-Yu Yan; Yu-Rong Tan; Xuan Gao; Dan Wang; Heng Zhang; Peng Wang; Shuang-Jiang Li; Yi Wang; Lu-Yao Zhou; Jin-Ping Liu (Biotechnology Letters, 2019)

Inverse Gaussian-beam common-reflection-point-stack imaging in crosswell seismic tomography - Zheng Rong Wei; Fei-Long Yang; Bao-Hua Liu; Yan-Liang Pei (Applied Geophysics, 2019)

The effect of ambient air pollution on circulatory mortality: a short-term exposure assessment in Xi’an, China - Kingsley Katleho Mokoena; Crystal Jane Ethan; Yan Yu; Karabo Shale; Yameng Fan; Feng Liu; Jie Rong (Environmental Science and Pollution Research, 2019)

Skin test of tuberculin purified protein derivatives with a dissolving microneedle-array patch - Wei Wang; Hou Ming Liu; Jing Zhou; Yu Guang Wang; Xi Feng; Hao Tang; Qinying Yan; Rong Sheng Zhu; Yu Wei Wu; Xing Guo Wang; Dan He; Fan Chen (Drug Delivery and Translational Research, 2019)

Two new sesquiterpenes from cultures of the higher fungus Pholiota nameko - Xiao-Yan Yang; Wan-Rong Niu; Rui-Ting Li; Xiu-Ming Cui; Ji-Kai Liu (Natural Product Research, 2019)

Species with moderate intraspecific trait variability are locally abundant within an environmentally heterogeneous subtropical forest - Guochun Shen; En-Rong Yan; Avi Bar-Massada; Jian Zhang; Heming Liu; Xihua Wang; Mingshan Xu (Oecologia, 2019)

Hydrogen peroxide and nitric oxide are involved in programmed cell death induced by cryopreservation in Dendrobium protocorm-like bodies - Xue-ru Jiang; Rui-fen Ren; Wei Di; Meng-xue Jia; Ze-di Li; Yan Liu; Rong-fu Gao (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Hyperinsulinemia-induced KLF5 mediates endothelial angiogenic dysfunction in diabetic endothelial cells - Xi-hui Wang; Chang-you Yan; Jian-rong Liu (Journal of Molecular Histology, 2019)

New pyrazinoquinazoline alkaloids Isolated from a culture of Stenotrophomonas maltophilia QB-77 - Sheng-Yan Qian; Cai-Ling Yang; Afsar Khan; Rong-Xiang Chen; Ming-Song Wu; Li Tuo; Qian Wang; Jian-Guo Liu; Gui-Guang Cheng (Natural Product Research, 2019)

Reduced thiamine binding is a novel mechanism for TPK deficiency disorder - Wenjie Huang; Jiao Qin; Dingdong Liu; Yan Wang; Xiaofei Shen; Na Yang; Hui Zhou; Xiao-Tang Cai; Zhi-Ling Wang; Dan Yu; Rong Luo; Qingxiang Sun; et al. (Molecular Genetics and Genomics, 2019)

Incidence and clinical correlates of anger attacks in Chinese patients with obsessive-compulsive disorder - Ying-ying Zhang; Heng-fen Gong; Xiao-li Zhang; Wen-juan Liu; Hai-yan Jin; Fang Fang; Sophie Schneider; Elizabeth McIngvale; Chen-cheng Zhang; Wayne K. Goodman; Xi-rong Sun; Eric A. Storch (Journal of Zhejiang University-SCIENCE B, 2019)

Quantitative Vulnerability Model of Earth Dam Overtopping and its Application - Chong-Xun Mo; Gui-Yan Mo; Liu Peng; Qing Yang; Xin-Rong Zhu; Qing-Ling Jiang; Ju-Liang Jin (Water Resources Management, 2019)

RETRACTED ARTICLE: Ambient air pollution and adverse birth outcomes: a systematic review and meta-analysis - Le-Qian Guo; Yu Chen; Bai-Bing Mi; Shao-Nong Dang; Dou-Dou Zhao; Rong Liu; Hong-Li Wang; Hong Yan (Journal of Zhejiang University-SCIENCE B, 2019)

Molecular, functional, and gene expression analysis of zebrafish Ror1 receptor - Yan Bai; Chengdong Liu; Jianfeng Zhou; Xiaozhi Rong; Hongying Wang (Fish Physiology and Biochemistry, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

What drives low-carbon consumption behavior of Chinese college students? The regulation of situational factors - Yan Liu; Rong Liu; Xin Jiang (Natural Hazards, 2019)

Is Moss Stoichiometry Influenced by Microtopography in a Boreal Peatland of Northeast China? - Xinhou Zhang; Rong Mao; Changchun Song; Yan Liu; Zhaojie Ren (Chinese Geographical Science, 2018)

Frond transformation system mediated by Agrobacterium tumefaciens for Lemna minor - Gui-Li Yang; Yang Fang; Ya-Liang Xu; Li Tan; Qi Li; Yang Liu; Fan Lai; Yan-Ling Jin; An-Ping Du; Kai-Ze He; Xin-Rong Ma; Hai Zhao (Plant Molecular Biology, 2018)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Late spring soil moisture variation over the Tibetan Plateau and its influences on the plateau summer monsoon - Juan Zhou; Jun Wen; Rong Liu; Xin Wang; Yan Xie (International Journal of Climatology, 2018)
Based on the European Centre for Medium‐Range Weather Forecasts (ECMWF) ERA‐Interim reanalysis data from 1979 to 2016, an index for Tibetan Plateau (TP) soil moisture ( I TPSM ), which could represent inter‐annual variation in spring soil moisture, is defined after removing the linear trend in soil moisture. The late spring soil moisture variation over the TP and its influences on the plateau summer monsoon are analysed. The results show that the TP soil moisture variation is non‐uniform, and spring soil moisture over the northeastern TP shows an increasing trend, while the western TP (especially the peripheral area) renders a significantly decreasing trend. When the I TPSM shows positive (negative) anomalies (i.e., spring soil moisture over the northeastern TP is higher (lower), soil moisture over the western TP is lower (higher) than normal), the plateau summer monsoon may be stronger (weaker). Anomalous variations in spring TP soil moisture can eventually affect the plateau summer monsoon by changing atmospheric circulation, diabatic heating, and water vapour transportation. It is found that when the I TPSM exhibits positive anomalies, diabatic heating over the centre and eastern TP is remarkably enhanced, and warm and humid moisture from the Bay of Bengal and Arabian Sea and cold air from high latitudes merge over the central and eastern TP; coupled with lower‐level convergence and upper‐level divergence, all these contribute to an increase in plateau summer monsoonal precipitation. When the I TPSM shows negative anomalies, diabatic heating over the centre and eastern TP is weakened, the anomalous cyclone to the south of the TP hinders warm and humid air flows transportation to the TP, and the anomalous anticyclone to the southeast of Lake Baikal weakens cold air to the south; coupled with weakened convergence and upwards motion, these factors all lead to a decrease in plateau summer monsoonal precipitation.

Fisheries in Chinese seas: What can we learn from controversial official fisheries statistics? - Bin Kang; Min Liu; Xiao-Xia Huang; Jun Li; Yun-Rong Yan; Chiao-Chuan Han; Shao-Bo Chen (Reviews in Fish Biology and Fisheries, 2018)

Co-targeting PLK1 and mTOR induces synergistic inhibitory effects against esophageal squamous cell carcinoma - Ting-Ting Liu; Kai-Xia Yang; Jing Yu; Ying-Ya Cao; Jian-Song Ren; Jia-Jie Hao; Bei-Qing Pan; Sai Ma; Li-Yan Yang; Yan Cai; Ming-Rong Wang; Yu Zhang (Journal of Molecular Medicine, 2018)

Autophagic Modulation by Trehalose Reduces Accumulation of TDP-43 in a Cell Model of Amyotrophic Lateral Sclerosis via TFEB Activation - Ying Wang; Feng-Tao Liu; Yi-Xuan Wang; Rong-Yuan Guan; Chen Chen; Da-Ke Li; Lu-Lu Bu; Jie Song; Yu-Jie Yang; Yi Dong; Yan Chen; Jian Wang (Neurotoxicity Research, 2018)

Selective and novel cyclin-dependent kinases 4 inhibitor: synthesis and biological evaluation - Qingxiang Guo; Yongtao Li; Chao Zhang; Zhi Huang; Xin Wang; Yongwei Nie; Yao Li; Yanhua Liu; Shengyong Yang; Rong Xiang; Yan Fan (Medicinal Chemistry Research, 2018)

Protective effect of the total flavonoids from Apocynum venetum L. on carbon tetrachloride-induced hepatotoxicity in vitro and in vivo - Wei Zhang; Zheng Dong; Xiujuan Chang; Cuihong Zhang; Guanghua Rong; Xudong Gao; Zhen Zeng; Chunping Wang; Yan Chen; Yihui Rong; Jianhui Qu; Ze Liu; et al. (Journal of Physiology and Biochemistry, 2018)

Protein nutritional value, polyphenols and antioxidant properties of corn fermented with Agaricus brasiliensis and Agaricus bisporus - Fei-Hong Zhai; Hong-Yan Liu; Jian-Rong Han (World Journal of Microbiology and Biotechnology, 2018)

Linking intraspecific trait variability and spatial patterns of subtropical trees - En-Rong Yan; Liu-Li Zhou; Han Y. H. Chen; Xi-Hua Wang; Xiang-Yu Liu (Oecologia, 2018)

TNF-α/TNFR1 Signaling is Required for the Full Expression of Acute and Chronic Itch in Mice via Peripheral and Central Mechanisms - Xiuhua Miao; Ya Huang; Teng-Teng Liu; Ran Guo; Bing Wang; Xue-Long Wang; Li-Hua Chen; Yan Zhou; Ru-Rong Ji; Tong Liu (Neuroscience Bulletin, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

β-Arrestin-1 deficiency ameliorates renal interstitial fibrosis by blocking Wnt1/β-catenin signaling in mice - Huiyan Xu; Quanxin Li; Jiang Liu; Jiaqing Zhu; Liang Li; Ziying Wang; Yan Zhang; Yu Sun; Jinpeng Sun; Rong Wang; Fan Yi (Journal of Molecular Medicine, 2018)

Fertility outcomes in infertile women with complex hyperplasia or complex atypical hyperplasia who received progestin therapy and in vitro fertilization - Miao Li; Jia-lun Song; Ying Zhao; She-ling Wu; Hong-bin Liu; Rong Tang; Lei Yan (Journal of Zhejiang University-SCIENCE B, 2017)

Changes in the Intestinal Microbiota of Gibel Carp (Carassius gibelio) Associated with Cyprinid herpesvirus 2 (CyHV-2) Infection - Rong She; Tong-Tong Li; Dan Luo; Jia-Bao Li; Liu-Yi Yin; Huan Li; Yao-Min Liu; Xiang-Zhen Li; Qi-gui Yan (Current Microbiology, 2017)

Reduced weed seed shattering by silencing a cultivated rice gene: strategic mitigation for escaped transgenes - Huanxin Yan; Lei Li; Ping Liu; Xiaoqi Jiang; Lei Wang; Jia Fang; Zhimin Lin; Feng Wang; Jun Su; Bao-Rong Lu (Transgenic Research, 2017)

Globular adiponectin inhibits leptin-stimulated esophageal adenocarcinoma cell proliferation via adiponectin receptor 2-mediated suppression of UHRF1 - Jun Wang; Yan Cheng; Xiaoran Yin; Jie Wu; Yumei Luo; Jing Wu; Jia Di; Dong Liu; Yahui Huang; Rong Zhang; Jun Zhang (Molecular and Cellular Biochemistry, 2017)

Characterization of a Gallid herpesvirus 2 strain with novel reticuloendotheliosis virus long terminal repeat inserts - Yan-ping Zhang; Ke-yan Bao; Guo-rong Sun; Hong-chao Lv; Hong-yu Cui; Yu-long Gao; Xiao-mei Wang; Chang-jun Liu (Virus Genes, 2017)

Microglia activation contributes to quinolinic acid-induced neuronal excitotoxicity through TNF-α - Wei Feng; Yan Wang; Zi-Qi Liu; Xuan Zhang; Rong Han; You-Zhu Miao; Zheng-Hong Qin (Apoptosis, 2017)

A Volumetric and Functional Connectivity MRI Study of Brain Arginine-Vasopressin Pathways in Autistic Children - Xiao-Jing Shou; Xin-Jie Xu; Xiang-Zhu Zeng; Ying Liu; Hui-Shu Yuan; Yan Xing; Mei-Xiang Jia; Qing-Yun Wei; Song-Ping Han; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2017)

Bispectral index-guided sedation in transfemoral transcatheter aortic valve implantation: a retrospective control study - Wei He; Rong-rong Huang; Qing-yu Shi; Xian-bao Liu; Jian-an Wang; Min Yan (Journal of Zhejiang University-SCIENCE B, 2017)

Zebrafish phosvitin-derived peptide Pt5 inhibits melanogenesis via cAMP pathway - Yuan-Yuan Liu; Xiu-Rong Su; Shou-Sheng Liu; Shuang-Shuang Yang; Cheng-Yan Jiang; Yu Zhang; Shicui Zhang (Fish Physiology and Biochemistry, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Outbreak of severe pseudorabies virus infection in pig-offal-fed farmed mink in Liaoning Province, China - Hao Liu; Xin-Tong Li; Bo Hu; Xiao-Yu Deng; Lei Zhang; Shi-Zhen Lian; Hai-Ling Zhang; Shuang Lv; Xiang-Hong Xue; Rong-Guang Lu; Ning Shi; Ming-Hao Yan; et al. (Archives of Virology, 2017)

The effect of light on the cellular stoichiometry of Chlorella sp. in different growth phases: implications of nutrient drawdown in batch experiments - Jing Liu; Zhe Li; Jing-song Guo; Yan Xiao; Fang Fang; Rong-cong Qin; Ling-ling Zhang (Journal of Applied Phycology, 2017)

Accelerating Regulated Bioanalysis for Biotherapeutics: Case Examples Using a Microfluidic Ligand Binding Assay Platform - Rong Liu; Brian Hoffpauir; Shannon D Chilewski; Janice Gamberdella; Uma Kavita; Jia Duo; Carol Gleason; Yan Zhang; Renuka Pillutla; Binodh DeSilva; Lora Hamuro (The AAPS Journal, 2017)

Trichoderma harzianum-induced resistance against Fusarium oxysporum involves regulation of nuclear DNA content, cell viability and cell cycle-related genes expression in cucumber roots - Shuang-Chen Chen; Hong-Jiao Zhao; Zhong-Hong Wang; Cai-Xia Zheng; Pu-Yan Zhao; Zhi-Hua Guan; Hai-Yang Qin; Ai-Rong Liu; Xiao-Min Lin; Golam-Jalal Ahammed (European Journal of Plant Pathology, 2017)

Brain natriuretic peptide for prevention of contrast-inducednephropathy: a meta-analysis of randomized controlled trials - Xue-biao Wei; Lei Jiang; Xin-rong Liu; Dan-qing Yu; Ning Tan; Ji-yan Chen; Ying-ling Zhou; Peng-cheng He; Yuan-hui Liu (European Journal of Clinical Pharmacology, 2016)

Antidepressant-like effects of standardized gypenosides: involvement of brain-derived neurotrophic factor signaling in hippocampus - Rong-Hao Mu; Xiao-Yan Fang; Shuang-Shuang Wang; Cheng-Fu Li; Shao-Mei Chen; Xue-Mei Chen; Qing Liu; Yu-Cheng Li; Li-Tao Yi (Psychopharmacology, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

DNA-Binding, Photocleavage, and Photodynamic Anti-cancer Activities of Pyridyl Corroles - Zhen-Hua Liang; Hai-Yang Liu; Rong Zhou; Zao Zhang; Atif Ali; Bing-Jie Han; Yun-Jun Liu; Xin-Yan Xiao (The Journal of Membrane Biology, 2016)

Relationship between leaf reddening, ROS and antioxidants in Buxus microphylla during overwintering - Xue-ru Jiang; Jin-gen Peng; Meng-xue Jia; Yan Liu; Ling Guo; Rong-fu Gao (Acta Physiologiae Plantarum, 2016)

To perceive a perfect Dora Maar in peripheral vision - Rong-Ding He; Tao Su; Yang Yang; Ying Liu; Yan Wei; Rong-Qiao He (Science China Life Sciences, 2016)

Co-expression of MtDREB1C and RcXET Enhances Stress Tolerance of Transgenic China Rose (Rosa chinensis Jacq.) - Ji-Ren Chen; Yan-Bin Chen; Monika Ziemiańska; Rong Liu; Zi-Niu Deng; Irena Niedźwiecka-Filipiak; Yan-Lin Li; Jin-Xia Jiao; Xing-Yao Xiong (Journal of Plant Growth Regulation, 2016)

Heat shock protein 70 inhibits cardiomyocyte necroptosis through repressing autophagy in myocardial ischemia/reperfusion injury - Xiaojuan Liu; Chao Zhang; Chi Zhang; Jingjing Li; Wanwan Guo; Daliang Yan; Chen Yang; Jianhua Zhao; Tian Xia; Yuqing Wang; Rong Xu; Xiang Wu; et al. (In Vitro Cellular & Developmental Biology - Animal, 2016)

Cadmium Accumulation Kinetics in Rhodococcus jostii RHA1 and Potential Effects of Brominated Flame Retardants - Shen Xu; Zhong-Bo Wei; Lian-Hong Wang; Rong Ji; Liu-Yan Yang; Ai-Jun Miao (Water, Air, & Soil Pollution, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Effects of silica exposure on the cardiac and renal inflammatory and fibrotic response and the antagonistic role of interleukin-1 beta in C57BL/6 mice - Jiali Guo; Tingming Shi; Xiuqing Cui; Yi Rong; Ting Zhou; Zhihong Zhang; Yuewei Liu; Yan Shen; Weihong Chen (Archives of Toxicology, 2016)

Corilagin Protects Against HSV1 Encephalitis Through Inhibiting the TLR2 Signaling Pathways In Vivo and In Vitro - Yuan-Jin Guo; Tao Luo; Fei Wu; Huan Liu; Hua-Rong Li; Yuan-Wu Mei; Shu-Ling Zhang; Jun-Yan Tao; Ji-Hua Dong; Yuan Fang; Lei Zhao (Molecular Neurobiology, 2015)

Semaphorin 4A enhances lung fibrosis through activation of Akt via PlexinD1 receptor - Hai-Ying Peng; Wei Gao; Fa-Rong Chong; Hong-Yan Liu; Ji Zhang (Journal of Biosciences, 2015)

Retraction Note to: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2015)

Angiotensin II increases secreted frizzled-related protein 5 (sFRP5) expression through AT1 receptor/Rho/ROCK1/JNK signaling in cardiomyocytes - Xin Jin; Bingyan Guo; Jie Yan; Rong Yang; Liang Chang; Yaling Wang; Chenglong Miao; Suyun Liu; Hui Zhang; Yongjun Li (Molecular and Cellular Biochemistry, 2015)

Mapping quantitative trait loci (QTL) determining seed-shattering in weedy rice: evolution of seed shattering in weedy rice through de-domestication - Nan Yao; Lei Wang; Huanxin Yan; Yongsheng Liu; Bao-Rong Lu (Euphytica, 2015)

Inside out: high-efficiency plant regeneration and Agrobacterium-mediated transformation of upland and lowland switchgrass cultivars - Yan-Rong Liu; Hui-Fang Cen; Jian-Ping Yan; Yun-Wei Zhang; Wan-Jun Zhang (Plant Cell Reports, 2015)

Zinc binds to and directly inhibits protein phosphatase 2A in vitro - Yan Xiong; Dan-Ju Luo; Xiu-Lian Wang; Mei Qiu; Yang Yang; Xiong Yan; Jian-Zhi Wang; Qi-Fa Ye; Rong Liu (Neuroscience Bulletin, 2015)

Flavobacterium shanxiense sp. nov., Isolated from Soil - Fan Yang; Hong-ming Liu; Rong Zhang; Ding-bin Chen; Xiang Wang; Xin Yan; Qing Hong; Shun-peng Li (Current Microbiology, 2015)

Predicting hybrid fertility from maker-based genetic divergence index of parental varieties: implications for utilizing inter-subspecies heterosis in hybrid rice breeding - Ping Liu; Zhiwu Dan; Zhe Wang; Shaoqing Li; Nengwu Li; Huanxin Yan; Xingxing Cai; Bao-Rong Lu (Euphytica, 2015)

Expression and clinical role of TCTP in epithelial ovarian cancer - Chen Chen; Yan Deng; Minhui Hua; Qinghua Xi; Rong Liu; Shuyun Yang; Jian Liu; Jianxin Zhong; Meilan Tang; Shumin Lu; Zhimei Zhang; Xiao Min; et al. (Journal of Molecular Histology, 2015)

RNAi Knockdown of Hypoxia-Inducible Factor-1α Decreased the Proliferation, Migration, and Invasion of Hypoxic Hepatocellular Carcinoma Cells - ChengShi Chen; Rong Liu; JianHua Wang; ZhiPing Yan; Sheng Qian; Wei Zhang (Cell Biochemistry and Biophysics, 2015)

Cardiopulmonary Exercise Capacity and Ventilation Effectiveness in Patients after Clinical Cure of Acute Irritant Gas Poisoning - Rong Yan; Wenlan Yang; Jinming Liu; Beilan Gao; Kongrong Guo; Daoyuan Sun (Cell Biochemistry and Biophysics, 2015)

De novo analysis of the Tenebrio molitor (Coleoptera: Tenebrionidae) transcriptome and identification of putative glutathione S-transferase genes - Su Liu; Xiao-Xiao Shi; Yan-Dong Jiang; Zi-Jie Zhu; Ping Qian; Min-Jing Zhang; Hang Yu; Qing-Zi Zhu; Zhong-Jun Gong; Zeng-Rong Zhu (Applied Entomology and Zoology, 2015)

Effects of exogenous NO on the growth, mineral nutrient content, antioxidant system, and ATPase activities of Trifolium repens L. plants under cadmium stress - Shi-Liang Liu; Rong-Jie Yang; Ming-Dong Ma; Fang Dan; Yan Zhao; Pan Jiang; Mao-Hua Wang (Acta Physiologiae Plantarum, 2015)

Isolation and characterization of 10 polymorphic microsatellite loci from the Chinese ratsnake (Zaocys dhumnades) - Rong-Fang Wang; Chao-Nan Zhu; Zhe Liu; Yan-Fu Qu (Conservation Genetics Resources, 2014)

RNAi-directed downregulation of betaine aldehyde dehydrogenase 1 (OsBADH1) results in decreased stress tolerance and increased oxidative markers without affecting glycine betaine biosynthesis in rice (Oryza sativa) - Wei Tang; Jiaqi Sun; Jia Liu; Fangfang Liu; Jun Yan; Xiaojun Gou; Bao-Rong Lu; Yongsheng Liu (Plant Molecular Biology, 2014)

The rescuable function and mechanism of resveratrol on As2O3-induced hERG K+ channel deficiency - Xin Zhao; Kai-ping Zhang; Ting Huang; Cai-Chuan Yan; Li-Rong Liu; Qi-Lei Zhu; Feng-Feng Guo; Chen Liu; Bao-Xin Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Identification of a Novel Mutation in the Presenilin 1 Gene in a Chinese Alzheimer’s Disease Family - Bo Deng; Yan Lian; Xin Wang; Fan Zeng; Bin Jiao; Ye-Ran Wang; Chun-Rong Liang; Yu-Hui Liu; Xian-Le Bu; Xiu-Qing Yao; Chi Zhu; Lu Shen; et al. (Neurotoxicity Research, 2014)

ZSTK474, a novel PI3K inhibitor, modulates human CD14+ monocyte-derived dendritic cell functions and suppresses experimental autoimmune encephalomyelitis - Zhenyi Xue; Wen Li; Huafeng Wang; Biao Huang; Zhenzhen Ge; Chao Gu; Ying Liu; Kai Zhang; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; et al. (Journal of Molecular Medicine, 2014)

Isolation and characterization of microsatellite loci in the Ussuri mamushi (Gloydius ussuriensis) - Rong-Fang Wang; Yan-Qing Wu; Zhe Liu; Yan-Fu Qu (Conservation Genetics Resources, 2014)

Expression of TGF-β1, SNAI1 and MMP-9 is associated with lymph node metastasis in papillary thyroid carcinoma - Ni Wang; Rong Jiang; Jun-Yan Yang; Cui Tang; Lei Yang; Man Xu; Qi-Feng Jiang; Zhi-Min Liu (Journal of Molecular Histology, 2014)

Dynamic patterns of histone H3 lysine 4 methyltransferases and demethylases during mouse preimplantation development - Gen-Bao Shao; Jun-Chao Chen; Liu-Ping Zhang; Pan Huang; Hong-Yan Lu; Jie Jin; Ai-Hua Gong; Jian-Rong Sang (In Vitro Cellular & Developmental Biology - Animal, 2014)

Advances in preimplantation genetic diagnosis/screening - LiYing Yan; Yuan Wei; Jin Huang; XiaoHui Zhu; XiaoDan Shi; Xi Xia; Jie Yan; CuiLing Lu; Ying Lian; Rong Li; Ping Liu; Jie Qiao (Science China Life Sciences, 2014)

RETRACTED ARTICLE: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2014)

Regulatory effect of AMP-activated protein kinase on pulmonary hypertension induced by chronic hypoxia in rats: in vivo and in vitro studies - Xiaoying Huang; Rong Fan; Yuanyuan Lu; Chang Yu; Xiaomei Xu; Xie Zhang; Panpan Liu; Shuangquan Yan; Chun Chen; Liangxing Wang (Molecular Biology Reports, 2014)

Trehalose Metabolism-Related Genes in Maize - Mei-Liang Zhou; Qian Zhang; Zhan-Min Sun; Li-Hui Chen; Bo-Xin Liu; Kai-Xuan Zhang; Xue-Mei Zhu; Ji-Rong Shao; Yi-Xiong Tang; Yan-Min Wu (Journal of Plant Growth Regulation, 2014)

Large-scale screening maize germplasm for low-phosphorus tolerance using multiple selection criteria - Li-tian Zhang; Jia Li; Ting-zhao Rong; Shi-bin Gao; Feng-kai Wu; Jie Xu; Meng-lu Li; Mo-ju Cao; Jing Wang; Er-liang Hu; Ya-xi Liu; Yan-li Lu (Euphytica, 2014)

Systemic Evaluation of Hypoxic-Ischemic Brain Injury in Neonatal Rats - Ai-Hua Zhu; Yan-Rong Hu; Wei Liu; Feng Gao; Jian-Xin Li; Li-Hui Zhao; Gang Chen (Cell Biochemistry and Biophysics, 2014)

Response profiles of cytokines and chemokines against avian H9N2 influenza virus within the mouse lung - Rong Huang; Jiyuan Liu; Wei Liang; Airong Wang; Zhihao Liu; Yan Yang; Jing Lv; Ying Bao; Yanxia Gao; Zengmin Miao; Tongjie Chai (Medical Microbiology and Immunology, 2014)

Arbuscular mycorrhizal fungi: potential biocontrol agents against the damaging root hemiparasite Pedicularis kansuensis? - Xiao-Lin Sui; Ai-Rong Li; Yan Chen; Kai-Yun Guan; Lu Zhuo; Yan-Yan Liu (Mycorrhiza, 2014)

Effect of lithology and structure on seismic response of steep slope in a shaking table test - Han-xiang Liu; Qiang Xu; Yan-rong Li (Journal of Mountain Science, 2014)

Silencing Pax3 by shRNA inhibits the proliferation and differentiation of duck (Anas platyrhynchos) myoblasts - Rong-Ping Zhang; He-He Liu; Hao-Han Wang; Yan Wang; Chun-Chun Han; Liang Li; Hua He; Heng-Yong Xu; Feng Xu; Ji-Wen Wang (Molecular and Cellular Biochemistry, 2014)

Effect of Hyperoxia on the Viability and Proliferation of the Primary Type II Alveolar Epithelial Cells - Xiu-xiang Liu; Xiu-rong Yu; Xiu-hong Jia; Ke-xuan Wang; Zheng-yan Yu; Chang-jun Lv (Cell Biochemistry and Biophysics, 2013)

A Highly Selective Turn-On Fluorescent Chemosensor for Zinc Ion in Aqueous Media - Zeng-chen Liu; Zheng-yin Yang; Yan-xia Li; Bao-dui Wang; Yong Li; Tian-rong Li; Yong-jie Ding (Journal of Fluorescence, 2013)

Identification of differentially expressed genes in Brassica juncea var. tumida Tsen following infection by Plasmodiophora brassicae - Yuanli Luo; Youping Yin; Yan Liu; Xiaotu Pei; Zhongkang Wang; Yonghong Fan; Xuyi Wang; Rong Leng (European Journal of Plant Pathology, 2013)

Fine structure and primary sensory projections of sensilla located in the labial-palp pit organ of Helicoverpa armigera (Insecta) - Xin-Cheng Zhao; Qing-Bo Tang; Bente G. Berg; Yang Liu; Yan-Ru Wang; Feng-Ming Yan; Gui-Rong Wang (Cell and Tissue Research, 2013)

Relationship between cloud characteristics and radar reflectivity based on aircraft and cloud radar co-observations - Rong Zong; Liping Liu; Yan Yin (Advances in Atmospheric Sciences, 2013)

The association between CD14 gene C-260T polymorphism and coronary heart disease risk: a meta-analysis - Hong Pu; Jiong Yin; Yan Wu; Dongming Zhang; Yanian Wang; Rong Zhou; Lijuan Jiang; Yan Liu (Molecular Biology Reports, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Molecular and pathogenic characterization of new Xanthomonas oryzae pv. oryzae strains from the coastline region of Fangchenggang city in China - Shu-Qing Yang; Shu-Yan Liu; Shuai Zhao; Yan-Hua Yu; Rong-Bai Li; Cheng-Jie Duan; Ji-Liang Tang; Jia-Xun Feng (World Journal of Microbiology and Biotechnology, 2013)

Docking-based 3D-QSAR modeling of the inhibitors of IMP metallo-β-lactamase - Jiao Chen; Rong Yu; Bingzheng Shen; Yan Xu; Yifang Liu; Heng Zheng; Wenbing Yao (Medicinal Chemistry Research, 2013)

Lithium enhances TRAIL-induced apoptosis in human lung carcinoma A549 cells - Yan Lan; Xiufeng Liu; Rong Zhang; Kai Wang; Yao Wang; Zi-Chun Hua (BioMetals, 2013)

Lyssavirus surveillance in bats of southern China’s Guangxi Province - Zhuan-Ling Lu; Wen Wang; Wei-Li Yin; Hai-Bo Tang; Yan Pan; Xiang Liang; Qi Liu; Yi Xiong; Nobuyuki Minamoto; Ting Rong Luo (Virus Genes, 2013)

Pseudomonas aeruginosa isolates of distinct sub-genotypes exhibit similar potential of antimicrobial resistance by drugs exposure - Zhen-Hong Liu; Yan Xu; Li-Bo Duo; Yu Liu; Zhao-Zhen Xu; Jane L. Burns; Gui-Rong Liu; Bao-Feng Yang; Shu-Lin Liu (Antonie van Leeuwenhoek, 2013)

Rice choline monooxygenase (OsCMO) protein functions in enhancing glycine betaine biosynthesis in transgenic tobacco but does not accumulate in rice (Oryza sativa L. ssp. japonica) - Di Luo; Xiangli Niu; Jinde Yu; Jun Yan; Xiaojun Gou; Bao-Rong Lu; Yongsheng Liu (Plant Cell Reports, 2012)

Impact of nodular size on the predictive values of gray-scale, color-Doppler ultrasound, and sonoelastography for assessment of thyroid nodules - Yu-rong Hong; Yu-lian Wu; Zhi-yan Luo; Ning-bo Wu; Xue-ming Liu (Journal of Zhejiang University-SCIENCE B, 2012)

A role for anti-CD45RB monoclonal antibody treatment upon dendritic cells - Hui Qi; Jin-Peng Liu; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2012)

Genetic diversity analysis of Rhododendron aureum Georgi (Ericaceae) located on Changbai Mountain using ISSR and RAPD markers - Yan-Fei Liu; Ming Xing; Wei Zhao; Rong-Jun Fan; Su Luo; Xia Chen (Plant Systematics and Evolution, 2012)

Influence of education and working background on physicians’ knowledge of secondary prevention guidelines for coronary heart disease: results from a survey in China - Yan-jun Gong; Tao Hong; Jie Jiang; Rong-hui Yu; Yan Zhang; Zhao-ping Liu; Yong Huo (Journal of Zhejiang University-SCIENCE B, 2012)

Decreased expression of Beclin-1 and LC3 in human lung cancer - Zi-Feng Jiang; Li-Jie Shao; Wei-Min Wang; Xue-Bo Yan; Rong-Yu Liu (Molecular Biology Reports, 2012)

PTP1B inhibitor improves both insulin resistance and lipid abnormalities in vivo and in vitro - Yi-ming Ma; Rong-ya Tao; Qian Liu; Juan Li; Jin-ying Tian; Xiao-lin Zhang; Zhi-yan Xiao; Fei Ye (Molecular and Cellular Biochemistry, 2011)

Phenotypic and molecular characterization of rhizobacterium Burkholderia sp. strain R456 antagonistic to Rhizoctonia solani, sheath blight of rice - Bin Li; Bao-Ping Liu; Rong-Rong Yu; Miao-Miao Lou; Yan-Li Wang; Guan-Lin Xie; Hong-Ye Li; Guo-Chang Sun (World Journal of Microbiology and Biotechnology, 2011)

Analysis of variable sites between two complete South China tiger (Panthera tigris amoyensis) mitochondrial genomes - Wenping Zhang; Bisong Yue; Xiaofang Wang; Xiuyue Zhang; Zhong Xie; Nonglin Liu; Wenyuan Fu; Yaohua Yuan; Daqing Chen; Danghua Fu; Bo Zhao; Yuzhong Yin; et al. (Molecular Biology Reports, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Azoospermia related to a unique karyotype: 45,XY,−13,−19,+der(19)t(13;19)(q12;p13) - Chao Fu; Xin Yun; Yuan Dong; Bai-Yan Wu; Rong-Rong Han; Rui-Zhi Liu (Journal of Applied Genetics, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

Theoretical investigation of the first-shell mechanism of acetylene hydration catalyzed by a biomimetic tungsten complex - Yan-Fang Liu; Rong-Zhen Liao; Wan-Jian Ding; Jian-Guo Yu; Ruo-Zhuang Liu (JBIC Journal of Biological Inorganic Chemistry, 2011)

Kinetic analysis of γ-glutamyltransferase reaction process for measuring activity via an integration strategy at low concentrations of γ-glutamyl p-nitroaniline - Zhi-rong Li; Yin Liu; Xiao-lan Yang; Jun Pu; Bei-zhong Liu; Yong-hua Yuan; Yan-ling Xie; Fei Liao (Journal of Zhejiang University-SCIENCE B, 2011)

Anticancer Drug-Loaded Nanospheres Based on Biodegradable Amphiphilic ε-Caprolactone and Carbonate Copolymers - Guo-Ping Yan; Rong-Feng Zong; Liang Li; Ting Fu; Fan Liu; Xiang-Hua Yu (Pharmaceutical Research, 2010)

Differential miRNA expression and their target genes between NGX6-positive and negative colon cancer cells - Xiao-Yan Wang; Ming-Hua Wu; Fen Liu; Yu Li; Nan Li; Gui-Yuan Li; Shou-Rong Shen (Molecular and Cellular Biochemistry, 2010)

Laser altimetry data of Chang’E-1 and the global lunar DEM model - ChunLai Li; Xin Ren; JianJun Liu; XiaoDuan Zou; LingLi Mu; JianYu Wang; Rong Shu; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

A genome-wide association analysis implicates SOX6 as a candidate gene for wrist bone mass - LiJun Tan; Rong Liu; ShuFeng Lei; Rong Pan; TieLin Yang; Han Yan; YuFang Pei; Fang Yang; Feng Zhang; Feng Pan; YinPin Zhang; HongGang Hu; et al. (Science China Life Sciences, 2010)

Inhalable Microparticles as Carriers for Pulmonary Delivery of Thymopentin-Loaded Solid Lipid Nanoparticles - Yan-Zhen Li; Xun Sun; Tao Gong; Jie Liu; Jiao Zuo; Zhi-Rong Zhang (Pharmaceutical Research, 2010)

Chemometrics-based approach to modeling quantitative composition-activity relationships for Radix Tinosporae - Shi-Kai Yan; Zhong-Ying Lin; Wei-Xing Dai; Qi-Rong Shi; Xiao-Hua Liu; Hui-Zi Jin; Wei-Dong Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2010)

Differentiation and distribution of indica and japonica rice varieties along the altitude gradients in Yunnan Province of China as revealed by InDel molecular markers - Zhiyuan Xiong; Shujie Zhang; Yunyue Wang; Brian V. Ford-Lloyd; Min Tu; Xin Jin; Yue Wu; Huanxin Yan; Xiao Yang; Ping Liu; Bao-Rong Lu (Genetic Resources and Crop Evolution, 2010)

Alternative splicing in exon 9 of glucocorticoid receptor pre-mRNA is regulated by SRp40 - Xue-Bo Yan; Chen-Hong Tang; Yan Huang; Hui Fang; Zhi-Qiang Yu; Li-Min Wu; Rong-Yu Liu (Molecular Biology Reports, 2010)

An investigation of hormesis of trichloroethylene in L-02 liver cells by differential proteomic analysis - Hai-Yan Huang; Jian-Jun Liu; Ren-Rong Xi; Xiu-Mei Xing; Jian-Hui Yuan; Lin-Qing Yang; Gong-Hua Tao; Chun-Mei Gong; Zhi-Xiong Zhuang (Molecular Biology Reports, 2009)

Increased expression of Toll-like receptors 4 and 9 in human lung cancer - Yan-Bei Zhang; Feng-Lian He; Ming Fang; Tian-Feng Hua; Bi-Dan Hu; Zhi-Hong Zhang; Qi Cao; Rong-Yu Liu (Molecular Biology Reports, 2009)

Effects of allicin on CYP2C19 and CYP3A4 activity in healthy volunteers with different CYP2C19 genotypes - Li-Jun Yang; Lan Fan; Zhao-Qian Liu; Yan-Mei Mao; Dong Guo; Li-Hui Liu; Zhi-Rong Tan; Liang Peng; Chun-Ting Han; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Intra-population genetic diversity of two wheatgrass species along altitude gradients on the Qinghai-Tibetan Plateau: its implication for conservation and utilization - Xue-Bing Yan; Yu-Xia Guo; Chong Zhao; Fa-Yang Liu; Bao-Rong Lu (Conservation Genetics, 2009)

Association of MYF5 and MYOD1 Gene Polymorphisms and Meat Quality Traits in Large White × Meishan F2 Pig Populations - Min Liu; Jian Peng; De-Quan Xu; Rong Zheng; Feng-E Li; Jia-Lian Li; Bo Zuo; Ming-Gang Lei; Yuan-Zhu Xiong; Chang-Yan Deng; Si-Wen Jiang (Biochemical Genetics, 2008)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Adenovirus-mediated PDCD5 gene transfer sensitizes K562 cells to apoptosis induced by idarubicin in vitro and in vivo - Guo-Rui Ruan; Hong-Shan Zhao; Yan Chang; Jin-Lan Li; Ya-Zhen Qin; Yan-Rong Liu; Shan-Shan Chen; Xiao-Jun Huang (Apoptosis, 2008)

Changes of Porcine Growth Hormone and Pituitary Nitrogen Monoxide Production as a Response to Cadmium Toxicity - Xin-Yan Han; Qi-Chun Huang; Bo-Jing Liu; Zi-Rong Xu; Yi-Zhen Wang (Biological Trace Element Research, 2007)

Lance-adams syndrome: a report of two cases - Yan-xing Zhang; Jian-ren Liu; Biao Jiang; Hui-qin Liu; Mei-ping Ding; Shui-jiang Song; Bao-rong Zhang; Hong Zhang; Bin Xu; Huai-hong Chen; Zhong-jin Wang; Jian-zheng Huang (Journal of Zhejiang University-SCIENCE B, 2007)

Intergeneration CAG expansion in a Wuhan juvenile-onset Huntington disease family - Yuan Liu; Yan Shen; He Li; Hui Wang; Zhen-Rong Yang; Yan Chen; Yan-Ping Tang (Neuroscience Bulletin, 2007)

Role of iNOS-derived reactive nitrogen species and resultant nitrative stress in leukocytes-induced cardiomyocyte apoptosis after myocardial ischemia/reperfusion - Xiao-Liang Wang; Hui-Rong Liu; Lin Tao; Feng Liang; Li Yan; Rong-Rui Zhao; Bernard L. Lopez; Theodore A. Christopher; Xin-Liang Ma (Apoptosis, 2007)

Effects of predator-mediated apparent competition on the population dynamics of Tetranychus urticae on apples - Chang-zhong Liu; Lin Yan; Hua-rong Li; Gang Wang (BioControl, 2006)

Rapid Detection of Avian Influenza Virus A and Subtype H5N1 by Single Step Multiplex Reverse Transcription-polymerase Chain Reaction - Hui-Ling Wei; Gui-Rong Bai; Aaron S. Mweene; Ying-Chun Zhou; Yan-Long Cong; Juan Pu; Shuai Wang; Hiroshi Kida; Jin-Hua Liu (Virus Genes, 2006)

Roots of pioneer trees in the lower sub-tropical area of Dinghushan, Guangdong, China - Yan-ru Hao; Shao-lin Peng; Jiang-ming Mo; Xin-wei Liu; Zhuo-quan Chen; Kai Zhou; Jin-rong Wu (Journal of Zhejiang University-SCIENCE B, 2006)

Genetic linkage of human height is confirmed to 9q22 and Xq24 - Yao-Zhong Liu; Peng Xiao; Yan-fang Guo; Dong-Hai Xiong; Lan-Juan Zhao; Hui Shen; Yong-Jun Liu; Volodymyr Dvornyk; Ji-Rong Long; Hong-Yi Deng; Jin-Long Li; Robert R. Recker; et al. (Human Genetics, 2006)

Differential expression of RAB5A in human lung adenocarcinoma cells with different metastasis potential - Li Yu; Feng Hui-chen; Yu Chen; Rong Zou; Song Yan; Liu Chun-xiang; Wang Wu-ru; Pu Li (Clinical & Experimental Metastasis, 1999)